Amyloidogenic amyloid-?-peptide variants induce microbial agglutination and exert antimicrobial activity - Spitzer, Philipp; Condic, Mateja; Herrmann, Martin; Oberstein, Timo; Scharin-Mehlmann, Marina; Gilbert, Daniel; Friedrich, Oliver; Groemer, Teja; Kornhuber, Johannes; Lang, Roland; Maler, Juan Manuel (Scientific Reports, 2016)
Amyloid-? (A?) peptides are the main components of the plaques found in the brains of patients with Alzheimer's disease. However, A? peptides are also detectable in secretory compartments and peripheral blood contains a complex mixture of more than 40 different modified and/or N- and C-terminally truncated A? peptides. Recently, anti-infective properties of A? peptides have been reported. Here, we investigated the interaction of A? peptides of different lengths with various bacterial strains and the yeast Candida albicans. The amyloidogenic peptides A?1-42, A?2-42, and A?3p-42 but not the non-amyloidogenic peptides A?1-40 and A?2-40 bound to microbial surfaces. As observed by immunocytochemistry, scanning electron microscopy and Gram staining, treatment of several bacterial strains and Candida albicans with A? peptide variants ending at position 42 (A?x-42) caused the formation of large agglutinates. These aggregates were not detected after incubation with A?x-40. Furthermore, A?x-42 exerted an antimicrobial activity on all tested pathogens, killing up to 80% of microorganisms within 6 h. A?1-40 only had a moderate antimicrobial activity against C. albicans. Agglutination of A?1-42 was accelerated in the presence of microorganisms. These data demonstrate that the amyloidogenic A?x-42 variants have antimicrobial activity and may therefore act as antimicrobial peptides in the immune system.
EVALuna2:7714

Analysis of Corynebacterium diphtheriae macrophage interaction: Dispensability of corynomycolic acids for inhibition of phagolysosome maturation and identification of a new gene involved in synthesis of the corynomycolic acid layer - Ott, Lisa; Hacker, Elena; Kunert, Timo; Karrington, Ian Alexander; Etschel, Philipp; Lang, Roland; Wiesmann, Veit; Wittenberg, Thomas; Singh, Albel; Varela, Cristian; Bhatt, Apoorva; Sangal, Vartul; et al. (PLoS ONE, 2017)
EVALuna2:7740

A Severe Case of Tuberculosis Radiologically and Endoscopically Mimicking Colorectal Cancer with Peritoneal Carcinomatosis - Rath, Timo; Atreya, Raja; Geissdorfer, Walter; Lang, Roland; Nägel, Andreas; Neurath, Markus (Case Reports in Gastrointestinal Medicine, 2017)
Although generally rising in incidence, intestinal tuberculosis is still rare in western countries and due to unspecific manifestations mainly as ulcerations on endoscopy, diagnosis of intestinal tuberculosis is challenging. Within this report, we describe a case of severe intestinal tuberculosis radiologically and endoscopically masquerading as colorectal cancer with peritoneal carcinomatosis. Our case exemplifies that intestinal tuberculosis needs to be considered as a differential diagnosis in patients at risk and that undelayed and sensitive diagnosis of intestinal tuberculosis is of central importance for avoiding unfavorable disease outcome.
EVALuna2:33728

A Specific Reduction in Aβ1-42 vs. a Universal Loss of Aβ Peptides in CSF Differentiates Alzheimer's Disease From Meningitis and Multiple Sclerosis - Spitzer, Philipp; Lang, Roland; Oberstein, Timo; Lewczuk, Piotr; Ermann, Natalia; Huttner, Hagen; Masouris, Ilias; Kornhuber, Johannes; Koedel, Uwe; Maler, Juan M. (Frontiers in Aging Neuroscience, 2018)
A reduced concentration of Aβ1-42 in CSF is one of the established biomarkers of Alzheimer's disease. Reduced CSF concentrations of Aβ1-42 have also been shown in multiple sclerosis, viral encephalitis and bacterial meningitis. As neuroinflammation is one of the neuropathological hallmarks of Alzheimer's disease, an infectious origin of the disease has been proposed. According to this hypothesis, amyloid pathology is a consequence of a microbial infection and the resulting immune defense. Accordingly, changes in CSF levels of amyloid-β peptides should be similar in AD and inflammatory brain diseases. Aβ1-42 and Aβ1-40 levels were measured in cerebrospinal fluid by ELISA and Western blotting in 34 patients with bacterial meningitis (n = 9), multiple sclerosis (n = 5) or Alzheimer's disease (n = 9) and in suitable controls (n = 11). Reduced concentrations of Aβ1-42 were detected in patients with bacterial meningitis, multiple sclerosis and Alzheimer's disease. However, due to a concurrent reduction in Aβ1-40 in multiple sclerosis and meningitis patients, the ratio of Aβ1-42/Aβ1-40 was reduced only in the CSF of Alzheimer's disease patients. Urea-SDS-PAGE followed by Western blotting revealed that all Aβ peptide variants are reduced in bacterial meningitis, whereas in Alzheimer's disease, only Aβ1-42 is reduced. These results have two implications. First, they confirm the discriminatory diagnostic power of the Aβ1-42/Aβ1-40 ratio. Second, the differential pattern of Aβ peptide reductions suggests that the amyloid pathology in meningitis and multiple sclerosis differs from that in AD and does not support the notion of AD as an infection-triggered immunopathology.
EVALuna2:36428

Axonal Degeneration Is Regulated by a Transcriptional Program that Coordinates Expression of Pro- and Anti-degenerative Factors - Maor-Nof, Maya; Romi, Erez; Shalom, Hadas Sar; Ulisse, Valeria; Raanan, Calanit; Nof, Aviv; Leshkowitz, Dena; Lang, Roland; Yaron, Avraham (Neuron, 2016)
Developmental neuronal cell death and axonal elimination are controlled by transcriptional programs, of which their nature and the function of their components remain elusive. Here, we identified the dual specificity phosphatase Dusp16 as part of trophic deprivation-induced transcriptome in sensory neurons. Ablation of Dusp16 enhanced axonal degeneration in response to trophic withdrawal, suggesting that it has a protective function. Moreover, axonal skin innervation was severely reduced while neuronal elimination was increased in the Dusp16 knockout. Mechanistically, Dusp16 negatively regulates the transcription factor p53 and antagonizes the expression of the pro-degenerative factor, Puma (p53 upregulated modulator of apoptosis). Co-ablation of Puma with Dusp16 protected axons from rapid degeneration and specifically reversed axonal innervation loss early in development with no effect on neuronal deficits. Overall, these results reveal that physiological axonal elimination is regulated by a transcriptional program that integrates regressive and progressive elements and identify Dusp16 as a new axonal preserving factor.
EVALuna2:7745

Can Perfusion-Based Brain Tissue Oxygenation MRI Support the Understanding of Cerebral Abscesses In Vivo? - Knott, Michael; Hölter, Philip; Soder, Liam; Schlaffer, Sven-Martin; Hoffmanns, Sophia; Lang, Roland; Dörfler, Arnd; Schmidt, Manuel (Diagnostics, 2023)
Purpose: The clinical condition of a brain abscess is a potentially life-threatening disease. The combination of MRI-based imaging, surgical therapy and microbiological analysis is critical for the treatment and convalescence of the individual patient. The aim of this study was to evaluate brain tissue oxygenation measured with dynamic susceptibility contrast perfusion weighted imaging (DSC-PWI) in patients with brain abscess and its potential benefit for a better understanding of the environment in and around brain abscesses. Methods: Using a local database, 34 patients (with 45 abscesses) with brain abscesses treated between January 2013 and March 2021 were retrospectively included in this study. DSC-PWI imaging and microbiological work-up were key inclusion criteria. These data were analysed regarding a correlation between DSC-PWI and microbiological result by quantifying brain tissue oxygenation in the abscess itself, the abscess capsula and the surrounding oedema and by using six different parameters (CBF, CBV, CMRO2, COV, CTH and OEF). Results: Relative cerebral blood flow (0.335 [0.18–0.613] vs. 0.81 [0.49–1.08], p = 0.015), relative cerebral blood volume (0.44 [0.203–0.72] vs. 0.87 [0.67–1.2], p = 0.018) and regional cerebral metabolic rate for oxygen (0.37 [0.208–0.695] vs. 0.82 [0.55–1.19], p = 0.022) were significantly lower in the oedema around abscesses without microbiological evidence of a specific bacteria in comparison with microbiological positive lesions. Conclusions: The results of this study indicate a relationship between brain tissue oxygenation status in DSC-PWI and microbiological/inflammatory status. These results may help to better understand the in vivo environment of brain abscesses and support future therapeutic decisions.
CRIS-Team Scopus Importer:2023-11-24
Keywords: brain abscess; brain tissue oxygenation; DSC-PWI

Cd4+ T cells induced by tuberculosis subunit vaccine h1 can improve the hiv-1 env humoral response by intrastructural help - Klessing, Stephan; Temchura, Vladimir; Tannig, Pierre; Peter, Antonia Sophia; Christensen, Dennis; Lang, Roland; Überla, Klaus (Vaccines, 2020)
The induction of a potent and long-lasting, broadly neutralizing antibody response is one of the most promising approaches in HIV-1 vaccination. Recently, we demonstrated that Gagspecific T helper cells induced by DNA priming can enhance and modulate the HIV Env-specific B cell response upon virus-like particle (VLP) boost by intrastructural help (ISH). In order to minimize the induction of potentially harmful HIV specific TH cells, we explored the possibility to harness the heterologous TH cells induced by a recombinant tuberculosis subunit vaccine H1, which contains a fusion protein of Ag85B and ESAT-6 antigens in combination with the liposomal adjuvant CAF01. To provide ISH, immunodominant MHC-II restricted peptides from the H1 vaccine were genetically incorporated into the HIV 1 Gag protein and used for HIV VLP production. ISH effects on Envspecific antibody levels and B cell differentiation were analyzed in mice primed against H1 and boosted with VLPs. In contrast to non-primed mice, a significant increase of Env-specific IgG levels for up to 26 weeks after the last immunization was observed. This increase was largely caused by elevated IgG2b and IgG2c levels in mice that received H1 priming. Additionally, ISH enhanced the frequency of Env-specific long-lived plasma cells in the bone marrow. In this study, we were able to demonstrate that a heterologous prime-boost regimen consisting of the H1 tuberculosis subunit vaccine and T helper epitope modified HIV-1 VLPs resulted in enhanced HIV Env antibody and B cell responses, mediated by intrastructural help.
CRIS-Team Scopus Importer:2020-10-23
Keywords: H1 tuberculosis vaccine; HIV-1 vaccine; IgG isotype modulation; Intrastructural help

C/EBPβ regulates lipid metabolism and Pparg isoform 2 expression in alveolar macrophages - Dörr, Dorothea; Obermayer, Benedikt; Weiner, January Mikolaj; Zimmermann, Karin; Anania, Chiara; Wagner, Lisa Katharina; Lyras, Ekaterini Maria; Sapozhnikova, Valeriia; Lara-Astiaso, David; Prósper, Felipe; Lang, Roland; Lupiáñez, Darío G.; et al. (Science immunology, 2022)
Pulmonary alveolar proteinosis (PAP) is a syndrome characterized by accumulation of surfactant lipoproteins within the lung alveoli. Alveolar macrophages (AMs) are crucial for surfactant clearance, and their differentiation depends on colony-stimulating factor 2 (CSF2), which regulates the establishment of an AM-characteristic gene regulatory network. Here, we report that the transcription factor CCAAT/enhancer binding protein β (C/EBPβ) is essential for the development of the AM identity, as demonstrated by transcriptome and chromatin accessibility analysis. Furthermore, C/EBPβ-deficient AMs showed severe defects in proliferation, phagocytosis, and lipid metabolism, collectively resulting in a PAP-like syndrome. Mechanistically, the long C/EBPβ protein variants LAP* and LAP together with CSF2 signaling induced the expression of Pparg isoform 2 but not Pparg isoform 1, a molecular regulatory mechanism that was also observed in other CSF2-primed macrophages. These results uncover C/EBPβ as a key regulator of AM cell fate and shed light on the molecular networks controlling lipid metabolism in macrophages.
CRIS-Team Scopus Importer:2022-09-30

Class I myosin Myo1e regulates TLR4-triggered macrophage spreading, chemokine release, and antigen presentation via MHC class II - Wenzel, Jens; Ouderkirk, Jessica L.; Krendel, Mira; Lang, Roland (European Journal of Immunology, 2015)
TLR-mediated recognition of microbial danger induces substantial changes in macrophage migration, adherence, and phagocytosis. Recently, we described the LPS-regulated phosphorylation of many cytoskeleton-associated proteins by phosphoproteomics. The functional role of these cytoskeletal and motor proteins in innate immune cell responses is largely unexplored. Here, we first identified both long-tailed class I myosins Myo1e and Myo1f as important contributors to LPS-triggered macrophage spreading. Mouse bone marrow-derived macrophages and DCs deficient in Myo1e selectively secreted increased amounts of the chemokine CCL2. In addition, the cell surface expression of MHC class II (MHC-II) on both cell types was reduced in the absence of Myo1e. However, transcriptional changes in CCL2 and MHC-II were not observed in the absence of Myo1e, indicating that Myo1e regulates specific intracellular transport processes. The capacity of macrophages and DCs lacking Myo1e to stimulate antigen-specific CD4(+) T-cell proliferation was impaired, consistent with the reduced MHC-II surface protein levels. Surprisingly, in Myo1e-deficient DCs, the proteolytic cleavage of endocytosed antigen was also increased. Together, our results provide evidence for a non-redundant function of the motor protein Myo1e in the regulation of TLR4-controlled, cytoskeleton-associated functional properties of macrophages and DCs, and in induction of a full MHC-II-restricted adaptive immune response.
EVALuna2:7660

Comparison of the transcriptome, lipidome, and c-di-GMP production between BCGΔBCG1419c and BCG, with Mincle- and Myd88-dependent induction of proinflammatory cytokines in murine macrophages - Flores-Valdez, Mario Alberto; Peterson, Eliza J.R.; Aceves-Sánchez, Michel de Jesús; Baliga, Nitin S.; Morita, Yasu S.; Sparks, Ian L.; Saini, Deepak Kumar; Yadav, Rahul; Lang, Roland; Mata-Espinosa, Dulce; León-Contreras, Juan Carlos; Hernández-Pando, Rogelio (Scientific Reports, 2024)
We have previously reported the transcriptomic and lipidomic profile of the first-generation, hygromycin-resistant (HygR) version of the BCGΔBCG1419c vaccine candidate, under biofilm conditions. We recently constructed and characterized the efficacy, safety, whole genome sequence, and proteomic profile of a second-generation version of BCGΔBCG1419c, a strain lacking the BCG1419c gene and devoid of antibiotic markers. Here, we compared the antibiotic-less BCGΔBCG1419c with BCG. We assessed their colonial and ultrastructural morphology, biofilm, c-di-GMP production in vitro, as well as their transcriptomic and lipidomic profiles, including their capacity to activate macrophages via Mincle and Myd88. Our results show that BCGΔBCG1419c colonial and ultrastructural morphology, c-di-GMP, and biofilm production differed from parental BCG, whereas we found no significant changes in its lipidomic profile either in biofilm or planktonic growth conditions. Transcriptomic profiling suggests changes in BCGΔBCG1419c cell wall and showed reduced transcription of some members of the DosR, MtrA, and ArgR regulons. Finally, induction of TNF-α, IL-6 or G-CSF by bone-marrow derived macrophages infected with either BCGΔBCG1419c or BCG required Mincle and Myd88. Our results confirm that some differences already found to occur in HygR BCGΔBCG1419c compared with BCG are maintained in the antibiotic-less version of this vaccine candidate except changes in production of PDIM. Comparison with previous characterizations conducted by OMICs show that some differences observed in BCGΔBCG1419c compared with BCG are maintained whereas others are dependent on the growth condition employed to culture them.
CRIS-Team Scopus Importer:2024-06-14
Keywords: BCG; c-di-GMP; Cytokines; Lipids; RNASeq; Transcriptomic; Tuberculosis

Contact, Collaboration, and Conflict: Signal Integration of Syk-Coupled C-Type Lectin Receptors - Ostrop, Jenny; Lang, Roland (Journal of Immunology, 2017)
Several spleen tyrosine kinase-coupled C-type lectin receptors (CLRs) have emerged as important pattern recognition receptors for infectious danger. Because encounter with microbial pathogens leads to the simultaneous ligation of several CLRs and TLRs, the signals emanating from different pattern recognition receptors have to be integrated to achieve appropriate biological responses. In this review, we briefly summarize current knowledge about ligand recognition and core signaling by Syk-coupled CLRs. We then address mechanisms of synergistic and antagonistic crosstalk between different CLRs and with TLRs. Emerging evidence suggests that signal integration occurs through 1) direct interaction between receptors, 2) regulation of expression levels and localization, and 3) collaborative or conflicting signaling interference. Accordingly, we aim to provide a conceptual framework for the complex and sometimes unexpected outcome of CLR ligation in bacterial and fungal infection.
EVALuna2:7742

Contribution of MINCLE-SYK Signaling to Activation of Primary Human APCs by Mycobacterial Cord Factor and the Novel Adjuvant TDB - Ostrop, Jenny; Jozefowski, Katrin; Zimmermann, Stephanie; Hofmann, Katharina; Strasser, Erwin; Lepenies, Bernd; Lang, Roland (Journal of Immunology, 2015)
Trehalose-6,6-dimycolate (TDM), the mycobacterial cord factor, is an abundant cell wall glycolipid and major virulence factor of Mycobacterium tuberculosis. Its synthetic analog trehalose-6,6-dibehenate (TDB) is a new adjuvant currently in phase I clinical trials. In rodents, the C-type lectin receptors Mincle and Mcl bind TDB/TDM and activate macrophages and dendritic cells (DC) through the Syk-Card9 pathway. However, it is unknown whether these glycolipids activate human innate immune cells through the same mechanism. We performed in vitro analysis of TDB/TDM-stimulated primary human monocytes, macrophages, and DC; determined C-type lectin receptor expression; and tested the contribution of SYK, MINCLE, and MCL by small interfering RNA knockdown and genetic complementation. We observed a robust chemokine and cytokine release in response to TDB or TDM. MCSF-driven macrophages secreted higher levels of IL-8, IL-6, CCL3, CCL4, and CCL2 after stimulation with TDM, whereas DC responded more strongly to TDB and GM-CSF-driven macrophages were equally responsive to TDB and TDM. SYK kinase and the adaptor protein CARD9 were essential for glycolipid-induced IL-8 production. mRNA expression of MINCLE and MCL was high in monocytes and macrophages, with MINCLE and MCL proteins localized intracellularly under resting conditions. Small interfering RNA-mediated MINCLE or MCL knockdown caused on average reduced TDB- or TDM-induced IL-8 production. Conversely, retroviral expression in murine Mincle-deficient DC revealed that human MINCLE, but not MCL, was sufficient to confer responsiveness to TDB/TDM. Our study demonstrates that SYK-CARD9 signaling plays a key role in TDB/TDM-induced activation of innate immune cells in man as in mouse, likely by engagement of MINCLE.
EVALuna2:7676

Control of immune cell signaling by the immuno-metabolite itaconate - Lang, Roland; Siddique, Md Nur A Alam (Frontiers in Immunology, 2024)
Immune cell activation triggers signaling cascades leading to transcriptional reprogramming, but also strongly impacts on the cell’s metabolic activity to provide energy and biomolecules for inflammatory and proliferative responses. Macrophages activated by microbial pathogen-associated molecular patterns and cytokines upregulate expression of the enzyme ACOD1 that generates the immune-metabolite itaconate by decarboxylation of the TCA cycle metabolite cis-aconitate. Itaconate has anti-microbial as well as immunomodulatory activities, which makes it attractive as endogenous effector metabolite fighting infection and restraining inflammation. Here, we first summarize the pathways and stimuli inducing ACOD1 expression in macrophages. The focus of the review then lies on the mechanisms by which itaconate, and its synthetic derivatives and endogenous isomers, modulate immune cell signaling and metabolic pathways. Multiple targets have been revealed, from inhibition of enzymes to the post-translational modification of many proteins at cysteine or lysine residues. The modulation of signaling proteins like STING, SYK, JAK1, RIPK3 and KEAP1, transcription regulators (e.g. Tet2, TFEB) and inflammasome components (NLRP3, GSDMD) provides a biochemical basis for the immune-regulatory effects of the ACOD1-itaconate pathway. While the field has intensely studied control of macrophages by itaconate in infection and inflammation models, neutrophils have now entered the scene as producers and cellular targets of itaconate. Furthermore, regulation of adaptive immune responses by endogenous itaconate, as well as by exogenously added itaconate and derivatives, can be mediated by direct and indirect effects on T cells and antigen-presenting cells, respectively. Taken together, research in ACOD1-itaconate to date has revealed its relevance in diverse immune cell signaling pathways, which now provides opportunities for potential therapeutic or preventive manipulation of host defense and inflammation.
CRIS-Team Scopus Importer:2024-03-29
Keywords: ACOD1; IRG1; itaconate; macrophages; metabolism; post-translational modification; signal transduction; transport

Corrigendum: Dusp16 Deficiency Causes Congenital Obstructive Hydrocephalus and Brain Overgrowth by Expansion of the Neural Progenitor Pool - Zega, Ksenija; Jovanovic, Vukasin M.; Vitic, Zagorka; Niedzielska, Magdalena; Knaapi, Laura; Jukic, Marin M.; Partanen, Juha; Friedel, Roland H.; Lang, Roland; Brodski, Claude (Frontiers in Molecular Neuroscience, 2018)
[This corrects the article on p. 372 in vol. 10, PMID: 29170629.].
EVALuna2:36431

Cutting edge: Mincle is essential for recognition and adjuvanticity of the mycobacterial cord factor and its synthetic analog trehalose-dibehenate. - Schoenen, Hanne; Bodendorfer, Barbara; Hitchens, Kelly; Manzanero, Silvia; Werninghaus, Kerstin; Nimmerjahn, Falk; Agger, Else Marie; Stenger, Steffen; Andersen, Peter; Ruland, Juergen; Brown, Gordon D.; Wells, Christine; et al. (Journal of Immunology, 2010)
The mycobacterial cord factor trehalose-6,6-dimycolate (TDM) and its synthetic analog trehalose-6,6-dibehenate (TDB) are potent adjuvants for Th1/Th17 vaccination that activate Syk-Card9 signaling in APCs. In this study, we have further investigated the molecular mechanism of innate immune activation by TDM and TDB. The Syk-coupling adapter protein FcRgamma was essential for macrophage activation and Th17 adjuvanticity. The FcRgamma-associated C-type lectin receptor Mincle was expressed in macrophages and upregulated by TDM and TDB. Recombinant Mincle-Fc fusion protein specifically bound to the glycolipids. Genetic ablation of Mincle abolished TDM/TDB-induced macrophage activation and induction of T cell immune responses to a tuberculosis subunit vaccine. Macrophages lacking Mincle or FcRgamma were impaired in the inflammatory response to Mycobacterium bovis bacillus Calmette-Guérin. These results establish that Mincle is a key receptor for the mycobacterial cord factor and controls the Th1/Th17 adjuvanticity of TDM and TDB.
UnivIS-Import:2015-03-09:Pub.2010.med.IKMI.LHMMIPDR.cuttin

Cutting edge: TNF is essential for mycobacteria-induced MINCLE expression, macrophage activation, and Th17 adjuvanticity - Schick, Judith; Schäfer, Johanna; Alexander, Christian; Dichtl, Stefanie; Murray, Peter J.; Christensen, Dennis; Sorg, Ursula; Pfeffer, Klaus; Schleicher, Ulrike; Lang, Roland (Journal of Immunology, 2020)
TNF blockade is a successful treatment for human autoimmune disorders like rheumatoid arthritis and inflammatory bowel disease yet increases susceptibility to tuberculosis and other infections. The C-type lectin receptors (CLR) MINCLE, MCL, and DECTIN-2 are expressed on myeloid cells and sense mycobacterial cell wall glycolipids. In this study, we show that TNF is sufficient to upregulate MINCLE, MCL, and DECTIN-2 in macrophages. TNF signaling through TNFR1 p55 was required for upregulation of these CLR and for cytokine secretion in macrophages stimulated with the MINCLE ligand trehalose-6,6-dibehenate or infected with Mycobacterium bovis bacillus Calmette-Guérin. The Th17 response to immunization with the MINCLE dependent adjuvant trehalose-6,6-dibehenate was specifically abrogated in TNF-deficient mice and strongly attenuated by TNF blockade with etanercept. Together, interference with production or signaling of TNF antagonized the expression of DECTIN-2 family CLR, thwarting vaccine responses and possibly increasing infection risk.
CRIS-Team Scopus Importer:2020-07-31

Cytokine-dependent regulation of dendritic cell differentiation in the splenic microenvironment - Globisch, Theresa; Steiner, Nancy; Fuelle, Lorenz; Lukacs-Kornek, Veronika; Degrandi, Daniel; Dresing, Philipp; Alferink, Judith; Lang, Roland; Pfeffer, Klaus; Beyer, Marc; Weighardt, Heike; Kurts, Christian; et al. (European Journal of Immunology, 2014)
The DC-derived chemokine CCL17, a ligand of CCR4, has been shown to promote various inflammatory diseases such as atopic dermatitis, atherosclerosis, and inflammatory bowel disease. Under steady-state conditions, and even after systemic stimulation with LPS, CCL17 is not expressed in resident splenic DCs as opposed to CD8?(-) CD11b(+) LN DCs, which produce large amounts of CCL17 in particular after maturation. Upon systemic NKT cell activation through ?-galactosylceramide stimulation however, CCL17 can be upregulated in both CD8?(-) and CD8?(+) splenic DC subsets and enhances cross-presentation of exogenous antigens. Based on genome-wide expression profiling, we now show that splenic CD11b(+) DCs are susceptible to IFN-?-mediated suppression of CCL17, whereas LN CD11b(+) CCL17(+) DCs downregulate the IFN-?R and are much less responsive to IFN-?. Under inflammatory conditions, particularly in the absence of IFN-? signaling in IFN-?RKO mice, CCL17 expression is strongly induced in a major proportion of splenic DCs by the action of GM-CSF in concert with IL-4. Our findings demonstrate that the local cytokine milieu and differential cytokine responsiveness of DC subsets regulate lymphoid organ specific immune responses at the level of chemokine expression.
EVALuna2:7641

Deficiency of the microprocessor component DGCR8 impairs macrophage growth and unleashes IFN-dependent gene expression in response to mycobacteria - Killy, Barbara; Bodendorfer, B.; Pracht, Katharina; Jäck, Hans-Martin; Lang, Roland (EUROPEAN JOURNAL OF IMMUNOLOGY, 2019)
CRIS-Team WoS Importer:2019-10-08

Development of prevalence and incidence of non-tuberculous mycobacteria in German laboratories from 2016 to 2020 - Corbett, Caroline; Finger, Philipp; Heiß-Neumann, Marion; Bohnert, Juergen; Eder, Ines B.; Eisele, Melanie; Friesen, Inna; Kaasch, Achim J.; Kehrmann, Jan; Lang, Roland; Rödel, Jürgen; Roessler, Susann; et al. (Emerging Microbes & Infections, 2023)
Numbers of non-tuberculous mycobacteria (NTM) pulmonary diseases (PD) have been repeatedly reported as increasing over the last decades, particularly in Europe. Sound epidemiological data are however missing for most European regions. This study calculated prevalence and incidence of NTM recovered from patients’ lungs in Germany, the largest Central European country, over a five-year period. It furthermore determined regional particularities of NTM species and results from susceptibility testing. 22 German NTM laboratories provided their mycobacteriological diagnostic data of 11,430 NTM isolates recovered from 5998 pulmonary patients representing 30% of all notified NTM-PD cases of Germany from 2016 to 2020. NTM incidence and prevalence were calculated for every study year. The presented epidemiological indicators are particularly reliant as TB surveillance data were used as a reference and TB notification reaches almost 100% in Germany. Laboratory incidence and prevalence of NTM recovered from respiratory samples ranged from 4.5–4.9 and from 5.3–5.8/100,000 for the population of Germany, respectively, and did not change over the five-year study period. Prevalence and incidence were stable also when stratifying for facultative pathogenic NTM, M. avium/intracellulare complex (MAIC), and M. abscessus/chelonae complex (MABSC). The proportion of NTM with drug susceptibility testing (DST) increased from 27.3% (2016) to 43.8% (2020). The unchanging laboratory NTM prevalence/incidence in Germany represents a “ceiling” of possible NTM-PD notification when diagnostic strategies do not change in the coming years. A notable increase in NTM-DST may indicate better notification of NTM-PD and/or awareness of new clinical guidelines but still remains below clinical needs.
CRIS-Team Scopus Importer:2024-12-16
Keywords: drug susceptibility; incidence; Non-tuberculous mycobacteria; NTM-pulmonary disease; prevalence

DGCR8 deficiency impairs macrophage growth and unleashes the interferon response to mycobacteria - Killy, Barbara; Bodendorfer, Barbara; Mages, Jörg; Ritter, Kristina; Schreiber, Jonathan; Hölscher, Christoph; Pracht, Katharina; Ekici, Arif Bülent; Jäck, Hans-Martin; Lang, Roland (Life Science Alliance, 2021)
The mycobacterial cell wall glycolipid trehalose-6,6-dimycolate (TDM) activates macrophages through the C-type lectin receptor MINCLE. Regulation of innate immune cells relies on miRNAs, which may be exploited by mycobacteria to survive and replicate in macrophages. Here, we have used macrophages deficient in the microprocessor component DGCR8 to investigate the impact of miRNA on the response to TDM. Deletion of DGCR8 in bone marrow progenitors reduced macrophage yield, but did not block macrophage differentiation. DGCR8-deficient macrophages showed reduced constitutive and TDM-inducible miRNA expression. RNAseq analysis revealed that they accumulated primary miRNA transcripts and displayed a modest type I IFN signature at baseline. Stimulation with TDM in the absence of DGCR8 induced overshooting expression of IFNβ and IFN-induced genes, which was blocked by antibodies to type I IFN. In contrast, signaling and transcriptional responses to recombinant IFNβ were unaltered. Infection with live Mycobacterium bovis Bacille Calmette-Guerin replicated the enhanced IFN response. Together, our results reveal an essential role for DGCR8 in curbing IFNβ expression macrophage reprogramming by mycobacteria.
CRIS-Team Scopus Importer:2021-04-16

Differential control of Mincle-dependent cord factor recognition and macrophage responses by the transcription factors C/EBP? and HIF1? - Schoenen, Hanne Gunda; Huber, Alexandra; Sonda, Nada; Zimmermann, Stephanie; Jantsch, Jonathan; Lepenies, Bernd; Bronte, Vincenzo; Lang, Roland (Journal of Immunology, 2014)
Trehalose-6,6-dimycolate (TDM), the mycobacterial cord factor, and its synthetic analog Trehalose-6,6-dibehenate (TDB) bind to the C-type lectin receptors macrophage-inducible C-type lectin (Mincle) and Mcl to activate macrophages. Genetically, the transcriptional response to TDB/TDM has been defined to require FcR?-Syk-Card9 signaling. However, TDB/TDM-triggered kinase activation has not been studied well, and it is largely unknown which transcriptional regulators bring about inflammatory gene expression. In this article, we report that TDB/TDM caused only weak Syk-phosphorylation in resting macrophages, consistent with low basal Mincle expression. However, LPS-priming caused MYD88-dependent upregulation of Mincle, resulting in enhanced TDB/TDM-induced kinase activation and more rapid inflammatory gene expression. TLR-induced Mincle expression partially circumvented the requirement for Mcl in the response to TDB/TDM. To dissect transcriptional responses to TDB/TDM, we mined microarray data and identified early growth response (Egr) family transcription factors as direct Mincle target genes, whereas upregulation of Cebpb and Hif1a required new protein synthesis. Macrophages and dendritic cells lacking C/EBP? showed nearly complete abrogation of TDB/TDM responsiveness, but also failed to upregulate Mincle. Retroviral rescue of Mincle expression in Cebpb-deficient cells restored induction of Egr1, but not of G-CSF. This pattern of C/EBP? dependence was also observed after stimulation with the Dectin-1 ligand Curdlan. Inducible expression of hypoxia-inducible factor 1? (HIF1?) also required C/EBP?. In turn, HIF1? was not required for Mincle expression, kinase activation, and Egr1 or Csf3 expression, but critically contributed to NO production. Taken together, we identify C/EBP? as central hub in Mincle expression and inflammatory gene induction, whereas HIF1? controls Nos2 expression. C/EBP? also connects TLR signals to cord factor responsiveness through MYD88-dependent upregulation of Mincle.
EVALuna2:7659

Divergent effects of itaconate isomers on Coxiella burnetii growth in macrophages and in axenic culture - Siddique, Md Nur A Alam; Kellermeier, Fabian; Ölke, Martha; Zhao, Mingming; Büssow, Konrad; Oefner, Peter J.; Lührmann, Anja; Dettmer, Katja; Lang, Roland (Frontiers in Immunology, 2024)
Aconitate decarboxylase-1 (ACOD1) is expressed by activated macrophages and generates itaconate that exerts anti-microbial and immunoregulatory effects. ACOD1-itaconate is essential for macrophage-mediated control of the intracellular pathogen Coxiella (C.) burnetii, which causes Q fever. Two isomers of itaconate, mesaconate and citraconate, have overlapping yet distinct activity on macrophage metabolism and inflammatory gene expression. Here, we found that all three isomers inhibited the growth of C. burnetii in axenic culture in ACCM-2 medium. However, only itaconate reduced C. burnetii replication efficiently in Acod1-/- macrophages. In contrast, addition of citraconate strongly increased C. burnetii replication in Acod1+/- macrophages, whereas mesaconate weakly enhanced bacterial burden in Acod1-/- macrophages. Analysis of intracellular isomers showed that exogenous citraconate and mesaconate inhibited the generation of itaconate by infected Acod1+/- macrophages. Uptake of added isomers into Acod1-/- macrophages was increased after infection for itaconate and mesaconate, but not for citraconate. Mesaconate, but not citraconate, competed with itaconate for uptake into macrophages. Taken together, inhibition of itaconate generation by macrophages and interference with the uptake of extracellular itaconate could be identified as potential mechanisms behind the divergent effects of citraconate and mesaconate on C. burnetii replication in macrophages or in axenic culture.
CRIS-Team Scopus Importer:2024-08-30
Keywords: ACOD1; citraconate; infection; IRG1; itaconate; mesaconate; transport; uptake

Dual role of the mycobacterial cord factor TDM in cross-regulation of macrophage responses to IFN gamma - Killy, Barbara; Huber, Angelika; Ekici, Arif Bülent; Wirtz, Stefan; Dalpke, A.; Lang, Roland (2017)
EVALuna2:33888

Dual Specificity Phosphatases: From Molecular Mechanisms to Biological Function - Pulido, Rafael; Lang, Roland (International Journal of Molecular Sciences, 2019)
Dual specificity phosphatases (DUSPs) constitute a heterogeneous group of enzymes, relevant in human disease, which belong to the class I Cys-based group of protein tyrosine phosphatase (PTP) gene superfamily [...].
CRIS-Team Scopus Importer:2019-09-20

Dual-Specificity Phosphatases in Immunity and Infection: An Update - Lang, Roland; Raffi, Faizal A.M. (International Journal of Molecular Sciences, 2019)
Kinase activation and phosphorylation cascades are key to initiate immune cell activation in response to recognition of antigen and sensing of microbial danger. However, for balanced and controlled immune responses, the intensity and duration of phospho-signaling has to be regulated. The dual-specificity phosphatase (DUSP) gene family has many members that are differentially expressed in resting and activated immune cells. Here, we review the progress made in the field of DUSP gene function in regulation of the immune system during the last decade. Studies in knockout mice have confirmed the essential functions of several DUSP-MAPK phosphatases (DUSP-MKP) in controlling inflammatory and anti-microbial immune responses and support the concept that individual DUSP-MKP shape and determine the outcome of innate immune responses due to context-dependent expression and selective inhibition of different mitogen-activated protein kinases (MAPK). In addition to the canonical DUSP-MKP, several small-size atypical DUSP proteins regulate immune cells and are therefore also reviewed here. Unexpected and complex findings in DUSP knockout mice pose new questions regarding cell type-specific and redundant functions. Another emerging question concerns the interaction of DUSP-MKP with non-MAPK binding partners and substrate proteins. Finally, the pharmacological targeting of DUSPs is desirable to modulate immune and inflammatory responses.
CRIS-Team Scopus Importer:2019-06-21
Keywords: atypical DUSP; cytokines; inflammation; macrophage; MAPK phosphatase; T cell

Dusp16 Deficiency Causes Congenital Obstructive Hydrocephalus and Brain Overgrowth by Expansion of the Neural Progenitor Pool - Zega, Ksenija; Jovanovic, Vukasin M.; Vitic, Zagorka; Niedzielska, Magdalena; Knaapi, Laura; Jukic, Marin M.; Partanen, Juha; Friedel, Roland F.; Lang, Roland; Brodski, Claude (Frontiers in Molecular Neuroscience, 2017)
Hydrocephalus can occur in children alone or in combination with other neurodevelopmental disorders that are often associated with brain overgrowth. Despite the severity of these disorders, the molecular and cellular mechanisms underlying these pathologies and their comorbidity are poorly understood. Here, we studied the consequences of genetically inactivating in mice dual-specificity phosphatase 16 (Dusp16), which is known to negatively regulate mitogen-activated protein kinases (MAPKs) and which has never previously been implicated in brain development and disorders. Mouse mutants lacking a functionalDusp16gene (Dusp16-/-) developed fully-penetrant congenital obstructive hydrocephalus together with brain overgrowth. The midbrain aqueduct inDusp16-/-mutants was obstructed during mid-gestation by an expansion of neural progenitors, and during later gestational stages by neurons resulting in a blockage of cerebrospinal fluid (CSF) outflow. In contrast, the roof plate and ependymal cells developed normally. We identified a delayed cell cycle exit of neural progenitors inDusp16-/-mutants as a cause of progenitor overproliferation during mid-gestation. At later gestational stages, this expanded neural progenitor pool generated an increased number of neurons associated with enlarged brain volume. Taken together, we found thatDusp16plays a critical role in neurogenesis by balancing neural progenitor cell proliferation and neural differentiation. Moreover our results suggest that a lack of functionalDusp16could play a central role in the molecular mechanisms linking brain overgrowth and hydrocephalus.
EVALuna2:33301

Editorial: Lectins and Their Ligands in Shaping Immune Responses - Lepenies, Bernd; Lang, Roland (Frontiers in Immunology, 2019)
CRIS-Team Scopus Importer:2019-11-05
Keywords: C-type lectins; dendritic cells; galectins; glycoimmunology; immunomodulation; lectins; myeloid cells; siglecs

Enhancing automated micrograph-based evaluation of LPS-stimulated macrophage spreading - Held, Christian; Wenzel, Jens; Wiesmann, Veit; Palmisano, Ralf; Lang, Roland; Wittenberg, Thomas (Cytometry Part A, 2013)
To evaluate macrophage spreading in immunofluorescence images of macrophages for surface protein CD11b and nuclear counterstaining with DAPI, it is necessary to measure the size of the macrophages at different time points after stimulation. Manual evaluation of fluorescent micrographs is usually a time-consuming and error-prone task, with poor reproducibility. Automatic image analysis methods can be used to improve the results. The quality of the analysis with these methods mainly depends on the quality of the image segmentation. A segmentation and quantification scheme based on shading correction, k-means clustering, and fast marching level sets has been developed for the purpose. An initial application of this approach showed that separating touching and overlapping cells in particular suffers severely in the inevitably blurred conditions, leading to partly erroneous measurements of macrophage spreading. An alternative method of segmentation in fluorescent micrographs was therefore investigated and evaluated in this study. The proposed approach uses a methodology that separates foreground objects from background objects on the basis of Boykov's graph cuts. In this process, a rough estimation of background pixels is used for background seeds. To identify foreground seeds, a difference of Gaussian band pass filter based workflow is developed. Information on foreground and background seeds is then used for a gradient magnitude based graph cut resulting in a robust figure-ground separation method. In addition, a fast marching level set approach is used in the post-processing step, which makes it possible to split touching cells by incorporating information about the cell nuclei. An evaluation based on a total of 553 manually labeled macrophages depicted in 21 micrographs showed that the proposed method significantly improves segmentation and splitting performance for fluorescent micrographs of LPS-stimulated macrophages and reduces the rate of error in automated analysis of macrophage spreading in comparison with alternative methods. © 2013 International Society for Advancement of Cytometry.
UnivIS-Import:2015-04-14:Pub.2013.tech.IMMD.IMMD9.enhanc
Keywords: Fluorescence Microscopy; Image Processing; Computer Assisted Microscopy

Exploring the interrelationship between the skin microbiome and skin volatiles: A pilot study - Härtl, Tobias; Owsienko, Diana; Schwinn, Leo; Hirsch, Cathrin; Eskofier, Björn; Lang, Roland; Wirtz, Stefan; Loos, Helene (Frontiers in Ecology and Evolution, 2023)
Unravelling the interplay between a human’s microbiome and physiology is a relevant task for understanding the principles underlying human health and disease. With regard to human chemical communication, it is of interest to elucidate the role of the microbiome in shaping or generating volatiles emitted from the human body. In this study, we characterized the microbiome and volatile organic compounds (VOCs) sampled from the neck and axilla of ten participants (five male, five female) on two sampling days, by applying different methodological approaches. Volatiles emitted from the respective skin site were collected for 20 min using textile sampling material and analyzed on two analytical columns with varying polarity of the stationary phase. Microbiome samples were analyzed by a culture approach coupled with MALDI-TOF-MS analysis and a 16S ribosomal RNA gene (16S RNA) sequencing approach. Statistical and advanced data analysis methods revealed that classification of body sites was possible by using VOC and microbiome data sets. Higher classification accuracy was achieved by combination of both data pools. Cutibacterium, Staphylococcus, Micrococcus, Streptococcus, Lawsonella, Anaerococcus, and Corynebacterium species were found to contribute to classification of the body sites by the microbiome. Alkanes, esters, ethers, ketones, aldehydes and cyclic structures were used by the classifier when VOC data were considered. The interdisciplinary methodological platform developed here will enable further investigations of skin microbiome and skin VOCs alterations in physiological and pathological conditions.
CRIS-Team Scopus Importer:2023-02-17
Keywords: axilla; body odor; chemical communication; gas chromatography–mass spectrometry; multi-omic analyses; neck

Fatal Mycotic Aneurysm of the Basilar Artery Caused by Aspergillus fumigatus in a Patient with Pituitary Adenoma and Meningitis - Winterholler, Martin; Coras, Roland; Geißdörfer, Walter; Rammensee, Rudolf; Gölitz, Philipp; Bogdan, Christian; Lang, Roland (Frontiers in Medicine, 2017)
Fungal infections of the central nervous system (CNS) frequently occur in immunosuppressed patients. Here, we describe the case of an immunocompetent 64-year-old man who presented with diplopia, right-sided hemiparesis, and a mild headache after cleaning and replacing nesting boxes of wild birds during the preceding months. Lumbar puncture revealed pleocytosis, elevated protein, and lactate levels in the cerebrospinal fluid (CSF). Initial imaging showed ischemia in the left thalamus and an enlargement of the sellar region. Antibiotic treatment and corticosteroids led to an initial improvement but was followed by rapid deterioration. Antibiotic treatment was modified and antifungal therapy was added. Eighteen days after admission, the patient died from a subarachnoid hemorrhage resulting from the rupture of a fusiform aneurysm of the basilar artery. Microbiological culture of CSF was negative, but a positive galactomannan assay suggested fungal infection which was corroborated by detection of Aspergillus fumigatus DNA in pan-fungal PCR and sequencing. The presence of septated hyphae in the wall of the basilar artery confirmed the diagnosis of a mycotic aneurysm caused by hyphomycetal infection. In addition, brain autopsy revealed the presence of an invasive adrenocorticotrophic hormone-producing pituitary adenoma with arrosion of the sellar bone. This process and its invasiveness likely facilitated the spread of the fungal pathogen from the sphenoid sinus to the dura mater and finally led to cerebral angioinvasion. Our case demonstrates the challenge to timely diagnose and effectively treat aspergillosis as a cause of CNS infection also in apparently immunocompetent patients. The potential of assays detecting fungal antigens and of PCR to facilitate a timely diagnosis is discussed.
EVALuna2:7760

Ferritin-Mediated Iron Sequestration Stabilizes Hypoxia-Inducible Factor-1α upon LPS Activation in the Presence of Ample Oxygen. - Siegert, Isabel; Schödel, Johannes; Nairz, Manfred; Schatz, Valentin; Dettmer, Katja; Dick, Christopher; Kalucka, Joanna; Franke, Kristin; Ehrenschwender, Martin; Schley, Gunnar; Beneke, Angelika; Sutter, Jörg; et al. (Cell Reports, 2015)
Both hypoxic and inflammatory conditions activate transcription factors such as hypoxia-inducible factor (HIF)-1α and nuclear factor (NF)-κB, which play a crucial role in adaptive responses to these challenges. In dendritic cells (DC), lipopolysaccharide (LPS)-induced HIF1α accumulation requires NF-κB signaling and promotes inflammatory DC function. The mechanisms that drive LPS-induced HIF1α accumulation under normoxia are unclear. Here, we demonstrate that LPS inhibits prolyl hydroxylase domain enzyme (PHD) activity and thereby blocks HIF1α degradation. Of note, LPS-induced PHD inhibition was neither due to cosubstrate depletion (oxygen or α-ketoglutarate) nor due to increased levels of reactive oxygen species, fumarate, and succinate. Instead, LPS inhibited PHD activity through NF-κB-mediated induction of the iron storage protein ferritin and subsequent decrease of intracellular available iron, a critical cofactor of PHD. Thus, hypoxia and LPS both induce HIF1α accumulation via PHD inhibition but deploy distinct molecular mechanisms (lack of cosubstrate oxygen versus deprivation of co-factor iron).

Foxp1 controls mature B cell survival and the development of follicular and B-1 B cells - Patzelt, Thomas; Keppler, Selina J.; Gorka, Oliver; Thoene, Silvia; Wartewig, Tim; Reth, Michael; Foerster, Irmgard; Lang, Roland; Buchner, Maike; Ruland, Juergen (Proceedings of the National Academy of Sciences of the United States of America, 2018)
The transcription factor Foxp1 is critical for early B cell development. Despite frequent deregulation of Foxp1 in B cell lymphoma, the physiological functions of Foxp1 in mature B cells remain unknown. Here, we used conditional gene targeting in the B cell lineage and report that Foxp1 disruption in developing and mature B cells results in reduced numbers and frequencies of follicular and B-1 B cells and in impaired antibody production upon T cell-independent immunization in vivo. Moreover, Foxp1-deficient B cells are impaired in survival even though they exhibit an increased capacity to proliferate. Transcriptional analysis identified defective expression of the prosurvival Bcl-2 family gene Bcl2l1 encoding Bcl-xl in Foxp1-deficient B cells, and we identified Foxp1 binding in the regulatory region of Bcl2l1 Transgenic overexpression of Bcl2 rescued the survival defect in Foxp1-deficient mature B cells in vivo and restored peripheral B cell numbers. Thus, our results identify Foxp1 as a physiological regulator of mature B cell survival mediated in part via the control of Bcl-xl expression and imply that this pathway might contribute to the pathogenic function of aberrant Foxp1 expression in lymphoma.
EVALuna2:36430

Gene Trap Mice Reveal an Essential Function of Dual Specificity Phosphatase Dusp16/MKP-7 in Perinatal Survival and Regulation of Toll-like Receptor (TLR)-induced Cytokine Production - Niedzielska, Magdalena; Bodendorfer, Barbara; Muench, Sandra; Eichner, Alexander; Derigs, Marcus; Da Costa, Olivia; Schweizer, Astrid; Neff, Frauke; Nitschke, Lars; Sparwasser, Tim; Keyse, Stephen M.; Lang, Roland (Journal of Biological Chemistry, 2014)
MAPK activity is negatively regulated by members of the dual specificity phosphatase (Dusp) family, which differ in expression, substrate specificity, and subcellular localization. Here, we investigated the function of Dusp16/MKP-7 in the innate immune system. The Dusp16 isoforms A1 and B1 were inducibly expressed in macrophages and dendritic cells following Toll-like receptor stimulation. A gene trap approach was used to generate Dusp16-deficient mice. Homozygous Dusp16tp/tp mice developed without gross abnormalities but died perinatally. Fetal liver cells from Dusp16tp/tp embryos efficiently reconstituted the lymphoid and myeloid compartments with Dusp16-deficient hematopoietic cells. However, GM-CSF-induced proliferation of bone marrow progenitors in vitro was impaired in the absence of Dusp16. In vivo challenge with Escherichia coli LPS triggered higher production of IL-12p40 in mice with a Dusp16-deficient immune system. In vitro, Dusp16-deficient macrophages, but not dendritic cells, selectively overexpressed a subset of TLR-induced genes, including the cytokine IL-12. Dusp16-deficient fibroblasts showed enhanced activation of p38 and JNK MAPKs. In macrophages, pharmacological inhibition and siRNA knockdown of JNK1/2 normalized IL-12p40 secretion. Production of IL-10 and its inhibitory effect on IL-12 production were unaltered in Dusp16tp/tp macrophages. Altogether, the Dusp16 gene trap mouse model identifies an essential role in perinatal survival and reveals selective control of differentiation and cytokine production of myeloid cells by the MAPK phosphatase Dusp16.
EVALuna2:7642

Gut Pathobiont–Derived Outer Membrane Vesicles Drive Liver Inflammation and Fibrosis in Primary Sclerosing Cholangitis–Associated Inflammatory Bowel Disease - Dorner, Heidrun; Stolzer, Iris; Mattner, Jochen; Kaminski, Sophie; Leistl, Sofia; Edrich, Lisa-Maria; Schwendner, Raphael; Hobauer, Julia; Sebald, Adrian Thomas Erwin; Leikam, Stefanie; Gonzalez Acera, Miguel; Düll, Miriam; et al. (Gastroenterology, 2024)
Background & Aims: Primary sclerosing cholangitis (PSC), often associated with inflammatory bowel disease (IBD), presents a multifactorial etiology involving genetic, immunologic, and environmental factors. Gut dysbiosis and bacterial translocation have been implicated in PSC-IBD, yet the precise mechanisms underlying their pathogenesis remain elusive. Here, we describe the role of gut pathobionts in promoting liver inflammation and fibrosis due to the release of bacterial outer membrane vesicles (OMVs). Methods: Preclinical mouse models in addition to ductal organoids were used to acquire mechanistic data. A proof-of-concept study including serum and liver biopsies of a patient cohort of PSC (n = 22), PSC-IBD (n = 45), and control individuals (n = 27) was performed to detect OMVs in the systemic circulation and liver. Results: In both preclinical model systems and in patients with PSC-IBD, the translocation of OMVs to the liver correlated with enhanced bacterial sensing and accumulation of the NLRP3 inflammasome. Using ductal organoids, we were able to precisely attribute the pro-inflammatory and pro-fibrogenic properties of OMVs to signaling pathways dependent on Toll-like receptor 4 and NLRP3–gasdermin-D. The immunostimulatory potential of OMVs could be confirmed in macrophages and hepatic stellate cells. Furthermore, when we administered gut pathobiont–derived OMVs to Mdr2–/– mice, we observed a significant enhancement in liver inflammation and fibrosis. In a translational approach, we substantiated the presence of OMVs in the systemic circulation and hepatic regions of severe fibrosis using a PSC-IBD patient cohort. Conclusions: This study demonstrates the contribution of gut pathobionts in releasing OMVs that traverse the mucosal barrier and, thus, promote liver inflammation and fibrosis in PSC-IBD. OMVs might represent a critical new environmental factor that interacts with other disease factors to cause inflammation and thus define potential new targets for fibrosis therapy.
CRIS-Team Scopus Importer:2024-09-27
Keywords: Bacterial Extracellular Vesicle; Hepatic Inflammation; Inflammasome; PSC-IBD

Human skin dendritic cell fate is differentially regulated by the monocyte identity factor Kruppel-like factor 4 during steady state and inflammation - Jurkin, Jennifer; Krump, Corinna; Koeffel, Rene; Fieber, Christina; Schuster, Christopher; Brunner, Patrick M.; Borek, Izabela; Eisenwort, Gregor; Lim, Clarice; Mages, Joerg; Lang, Roland; Bauer, Wolfgang; et al. (Journal of Allergy and Clinical Immunology, 2017)
Langerhans cell (LC) networks play key roles in immunity and tolerance at body surfaces. LCs are established prenatally and can be replenished from blood monocytes. Unlike skin-resident dermal DCs (dDCs)/interstitial-type DCs and inflammatory dendritic epidermal cells appearing in dermatitis/eczema lesions, LCs lack key monocyte-affiliated markers. Inversely, LCs express various epithelial genes critical for their long-term peripheral tissue residency.Dendritic cells (DCs) are functionally involved in inflammatory diseases; however, the mechanisms remained poorly understood.In vitro differentiation models of human DCs, gene profiling, gene transduction, and immunohistology were used to identify molecules involved in DC subset specification.Here we identified the monocyte/macrophage lineage identity transcription factor Kruppel-like factor 4 (KLF4) to be inhibited during LC differentiation from human blood monocytes. Conversely, KLF4 is maintained or induced during dermal DC and monocyte-derived dendritic cell/inflammatory dendritic epidermal cell differentiation. We showed that in monocytic cells KLF4 has to be repressed to allow their differentiation into LCs. Moreover, respective KLF4 levels in DC subsets positively correlate with proinflammatory characteristics. We identified epithelial Notch signaling to repress KLF4 in monocytes undergoing LC commitment. Loss of KLF4 in monocytes transcriptionally derepresses Runt-related transcription factor 3 in response to TGF-?1, thereby allowing LC differentiation marked by a low cytokine expression profile.Monocyte differentiation into LCs depends on activation of Notch signaling and the concomitant loss of KLF4.
EVALuna2:7718

IgG subclass and vaccination stimulus determine changes in antigen specific antibody glycosylation in mice - Kao, Daniela; Lux, Anja; Schaffert, Anja; Lang, Roland; Altmann, Friedrich; Nimmerjahn, Falk (European Journal of Immunology, 2017)
Immunoglobulin G (IgG) glycosylation can modulate antibody effector functions. Depending on the precise composition of the sugar moiety attached to individual IgG glycovariants either pro- or anti-inflammatory effector pathways can be initiated via differential binding to type I or type II Fc-receptors. However, an in depth understanding of how individual IgG subclasses are glycosylated during the steady state and how their glycosylation pattern changes during vaccination is missing. To monitor IgG subclass glycosylation during the steady state and upon vaccination of mice with different T-cell dependent and independent antigens, tryptic digests of serum, and antigen-specific IgG preparations were analyzed by reversed phase-liquid chromatography-mass spectrometry. We show that there is a remarkable difference with respect to how individual IgG subclasses are glycosylated during the steady state. More importantly, upon T-cell dependent and independent vaccinations, individual antigen-specific IgG subclasses reacted differently with respect to changes in individual glycoforms, suggesting that the IgG subclass itself is a major determinant of restricting or allowing alterations in specific IgG glycovariants.
EVALuna2:7735

IKK? Promotes Intestinal Tumorigenesis by Limiting Recruitment of M1-like Polarized Myeloid Cells - Goektuna, Serkan I.; Canli, Ozge; Bollrath, Julia; Fingerle, Alexander A.; Horst, David; Diamanti, Michaela A.; Pallangyo, Charles; Bennecke, Moritz; Nebelsiek, Tim; Mankan, Arun K.; Lang, Roland; Artis, David; et al. (Cell Reports, 2014)
The recruitment of immune cells into solid tumors is an essential prerequisite of tumor development. Depending on the prevailing polarization profile of these infiltrating leucocytes, tumorigenesis is either promoted or blocked. Here, we identify I?B kinase ? (IKK?) as a central regulator of a tumoricidal microenvironment during intestinal carcinogenesis. Mice deficient in IKK? kinase activity are largely protected from intestinal tumor development that is dependent on the enhanced recruitment of interferon ? (IFN?)-expressing M1-like myeloid cells. In IKK? mutant mice, M1-like polarization is not controlled in a cell-autonomous manner but, rather, depends on the interplay of both IKK? mutant tumor epithelia and immune cells. Because therapies aiming at the tumor microenvironment rather than directly at the mutated cancer cell may circumvent resistance development, we suggest IKK? as a promising target for colorectal cancer (CRC) therapy.
EVALuna2:7655

IL-27 Induced by Select Candida spp. via TLR7/NOD2 Signaling and IFN-β Production Inhibits Fungal Clearance - Patin, Emmanuel C.; Jones, Adam V.; Thompson, Aiysha; Clement, Mathew; Liao, Chia-Te; Griffiths, James S.; Wallace, Leah E.; Bryant, Clare E.; Lang, Roland; Rosenstiel, Philip; Humphreys, Ian R.; Taylor, Philip R.; et al. (Journal of Immunology, 2016)
Candida spp. elicit cytokine production downstream of various pathogen recognition receptors, including C-type lectin-like receptors, TLRs, and nucleotide oligomerization domain (NOD)-like receptors. IL-12 family members IL-12p70 and IL-23 are important for host immunity against Candida spp. In this article, we show that IL-27, another IL-12 family member, is produced by myeloid cells in response to selected Candida spp. We demonstrate a novel mechanism for Candida parapsilosis-mediated induction of IL-27 in a TLR7-, MyD88-, and NOD2-dependent manner. Our data revealed that IFN-? is induced by C. parapsilosis, which in turn signals through the IFN-?/? receptor and STAT1/2 to induce IL-27. Moreover, IL-27R (WSX-1)-deficient mice systemically infected with C. parapsilosis displayed enhanced pathogen clearance compared with wild-type mice. This was associated with increased levels of proinflammatory cytokines in the serum and increased IFN-? and IL-17 responses in the spleens of IL-27R-deficient mice. Thus, our data define a novel link between C. parapsilosis, TLR7, NOD2, IFN-?, and IL-27, and we have identified an important role for IL-27 in the immune response against C. parapsilosis Overall, these findings demonstrate an important mechanism for the suppression of protective immune responses during infection with C. parapsilosis, which has potential relevance for infections with other fungal pathogens.
EVALuna2:7705

IL-33-induced metabolic reprogramming controls the differentiation of alternatively activated macrophages and the resolution of inflammation - Faas, Maria; Ipseiz, Natacha; Ackermann, Jochen; Culemann, Stephan; Grüneboom, Anika; Schröder, Fenja; Rothe, Tobias; Scholtysek, Carina; Eberhardt, Martin; Böttcher, Martin; Kirchner, Philipp; Stoll, Cornelia; et al. (Immunity, 2021)
Alternatively activated macrophages (AAMs) contribute to the resolution of inflammation and tissue repair. However, molecular pathways that govern their differentiation have remained incompletely understood. Here, we show that uncoupling protein-2-mediated mitochondrial reprogramming and the transcription factor GATA3 specifically controlled the differentiation of pro-resolving AAMs in response to the alarmin IL-33. In macrophages, IL-33 sequentially triggered early expression of pro-inflammatory genes and subsequent differentiation into AAMs. Global analysis of underlying signaling events revealed that IL-33 induced a rapid metabolic rewiring of macrophages that involved uncoupling of the respiratory chain and increased production of the metabolite itaconate, which subsequently triggered a GATA3-mediated AAM polarization. Conditional deletion of GATA3 in mononuclear phagocytes accordingly abrogated IL-33-induced differentiation of AAMs and tissue repair upon muscle injury. Our data thus identify an IL-4-independent and GATA3-dependent pathway in mononuclear phagocytes that results from mitochondrial rewiring and controls macrophage plasticity and the resolution of inflammation.
CRIS-Team Scopus Importer:2021-11-19
Keywords: alternatively activated macrophage; GATA3; interleukin-33; itaconate; mitochondrial rewiring; resolution of inlammation; UCP2; uncoupling

IL-4 and helminth infection downregulate MINCLE-dependent macrophage response to mycobacteria and Th17 adjuvanticity - Schick, Judith; Altunay, Meltem; Lacorcia, Matthew; Marschner, Nathalie; Westermann, Stefanie; Schluckebier, Julia; Schubart, Christoph; Bodendorfer, Barbara; Christensen, Dennis; Alexander, Christian; Wirtz, Stefan; Vöhringer, David; et al. (eLife, 2023)
The myeloid C-type lectin receptor (CLR) MINCLE senses the mycobacterial cell wall component trehalose-6,6'-dimycolate (TDM). Recently, we found that IL-4 downregulates MINCLE expression in macrophages. IL-4 is a hallmark cytokine in helminth infections, which appear to increase the risk for mycobacterial infection and active tuberculosis. Here, we investigated functional consequences of IL-4 and helminth infection on MINCLE-driven macrophage activation and Th1/Th17 adjuvanticity. IL-4 inhibited MINCLE and cytokine induction after macrophage infection with Mycobacterium bovis bacille Calmette-Guerin (BCG). Infection of mice with BCG upregulated MINCLE on myeloid cells, which was inhibited by IL-4 plasmid injection and by infection with the nematode Nippostrongylus brasiliensis in monocytes. To determine the impact of helminth infection on MINCLE-dependent immune responses, we vaccinated mice with a recombinant protein together with the MINCLE ligand trehalose-6,6-dibehenate (TDB) as adjuvant. Concurrent infection with N. brasiliensis or with Schistosoma mansoni promoted T cell-derived IL-4 production and suppressed Th1/Th17 differentiation in the spleen. In contrast, helminth infection did not reduce Th1/Th17 induction by TDB in draining peripheral lymph nodes, where IL-4 levels were unaltered. Upon use of the TLR4-dependent adjuvant G3D6A, N. brasiliensis infection impaired selectively the induction of splenic antigen-specific Th1 but not of Th17 cells. Inhibition of MINCLE-dependent Th1/Th17 responses in mice infected with N. brasiliensis was dependent on IL-4/IL-13. Thus, helminth infection attenuated the Th17 response to MINCLE-dependent immunization in an organ- and adjuvant-specific manner via the Th2 cytokines IL-4/IL-13. Taken together, our results demonstrate downregulation of MINCLE expression on monocytes and macrophages by IL-4 as a possible mechanism of thwarted Th17 vaccination responses by underlying helminth infection.
CRIS-Team Scopus Importer:2023-02-17
Keywords: C-type lectin receptors; co-infection; immunology; infectious disease; inflammation; microbiology; mouse; mycobacterial cord factor; Nippostrongylus brasiliensis; Schistosoma mansoni; Th cell differentiation

Inflammatory Properties and Adjuvant Potential of Synthetic Glycolipids Homologous to Mycolate Esters of the Cell Wall of Mycobacterium tuberculosis - Tima, Hermann Giresse; Al Dulayymi, Juma'A Raheem; Denis, Olivier; Lehebel, Pauline; Baols, Klarah Sherzad; Mohammed, Mohsin Omar; L'Homme, Laurent; Sahb, Mohaned Mohammed; Potemberg, Georges; Legrand, Sylvie; Lang, Roland; Beyaert, Rudi; et al. (Journal of Innate Immunity, 2017)
The cell wall of mycobacteria is characterised by glycolipids composed of different classes of mycolic acids (MAs; alpha-, keto-, and methoxy-) and sugars (trehalose, glucose, and arabinose). Studies using mutant Mtb strains have shown that the structure of MAs influences the inflammatory potential of these glycolipids. As mutant Mtb strains possess a complex mixture of glycolipids, we analysed the inflammatory potential of single classes of mycolate esters of the Mtb cell wall using 38 different synthetic analogues. Our results show that synthetic trehalose dimycolate (TDM) and trehalose, glucose, and arabinose monomycolates (TMM, GMM, and AraMM) activate bone marrow-derived dendritic cells in terms of the production of pro-inflammatory cytokines (IL-6 and TNF-?) and reactive oxygen species, upregulation of costimulatory molecules, and activation of NLRP3 inflammasome by a mechanism dependent on Mincle. These findings demonstrate that Mincle receptor can also recognise pentose esters and seem to contradict the hypothesis that production of GMM is an escape mechanism used by pathogenic mycobacteria to avoid recognition by the innate immune system. Finally, our experiments indicate that TMM and GMM, as well as TDM, can promote Th1 and Th17 responses in mice in an OVA immunisation model, and that further analysis of their potential as novel adjuvants for subunit vaccines is warranted.
EVALuna2:7739

Interdisciplinary symposium on challenges and opportunities for vaccines: A comprehensive approach of current and future vaccine strategies to improve vaccine effectiveness in complex chronic infectious contexts - Siebner, Alex S.; Habib, Marrium; Osmani, Vanesa; Adegnika, Ayola Akim; Bogdan, Christian; Breloer, Minka; Elliott, Alison; Fathi, Anahita; Hendrickx, Greet; Nono, Justin Komguep; Lang, Roland; Mayer, Johannes U.; et al. (Vaccine: X, 2025)
Vaccination is a key public health intervention, but vaccine immunogenicity, efficacy, and effectiveness vary geographically. These variations are not yet fully understood but are likely influenced by factors such as chronic infections, environmental and genetic differences, social and behavioral factors, and operational challenges, particularly in low- and middle-income countries (LMICs). To address these issues, the “International Symposium on Global Challenges and Opportunities for Vaccines” was held in Kloster Bernried, Germany, bringing together international scientists and stakeholders. Key discussions included: (1) Compromised vaccine immunogenicity due to helminth infections, (2) new vaccine approaches in vaccine development, (3) new frontiers in therapeutic vaccination, (4) challenges of vaccine trials, especially in low-resource settings, and (5) conceptualizing vaccine confidence in low and high resource contexts. The symposium highlighted the challenges of conducting vaccine trials in LMICs, such as participant follow-up, logistics, resources, and building trust. The main recommendation was to improve future vaccine trial designs through a comprehensive, interdisciplinary approach, including tools to evaluate vaccine immunogenicity, efficacy, and effectiveness.
CRIS-Team Scopus Importer:2025-03-14

Intestinal helminth co-infection and associated factors among pulmonary tuberculosis patients in Africa and Asia: a systematic review and meta-analysis - Zenebe, Yohannes; Habtamu, Meseret; Abebe, Markos; Tulu, Begna; Atnafu, Abay; Mekonnen, Daniel; Lang, Roland; Munshea, Abaineh (BMC Infectious Diseases, 2023)
Introduction: Tuberculosis (TB) and intestinal helminths have huge public health importance, and they are geographically overlapped. Data about the burden of intestinal helminth and TB co-infection in these areas are fragmented. In this systematic review and meta-analysis we compile the current literatures and generate pooled prevalence. We also identity factors associated with intestinal helminth co-infection among TB patients. Methods: Original articles published in English language up to March 23, 2022 were systematically searched from electronic database (PubMed/Medline, Scopus, Science Direct, Google Scholars and HINARI). The search was done using medical subject heading terms and keywords. Identified articles were exported into the EndNote library. The identified articles were screened using PRISMA flow diagram. Then the methodological quality of included articles was evaluated and rated using the modified version of Newcastle–Ottawa Scale. Data were extracted using Microsoft Excel. Sensitivity analysis and Egger regression test were used for the assessment of heterogeneity and publication bias. Finally the results are presented with a meta-analysis of pooled estimates, forest plots, and tables. The quantitative data were analyzed using Stata version 14. Results: From a total of 5457 searched articles, 22 eligible articles were included in the review. The pooled prevalence of helminth co-infection among TB cases was 29.69% (95%CI: 21.10, 38.29). TB patients were found to more frequently harbor one or more intestinal helminths than TB negative individuals (OR = 1.72 (95%CI: 1.20, 2.48)). Among the reported helminths, Schistosoma mansoni and Strongyloides stercoralis had the highest pooled prevalence among TB cases. However, unlike other individual helminths, only Strongyloides stercoralis (OR = 2.67 (95% CI, 1.20–6.76)) had significant association with TB cases compared to TB negatives. BMI was significantly associated with intestinal helminth co-infection among TB patients (OR = 2.75 (95%CI: 1.19, 6.38)). Conclusions: Patients with TB have been shown to harbor co-infection with one or more intestinal helminths with considerable proportions when compared with TB-negative individuals. The higher prevalence of helminth infection in TB cases might indicate that co-infection promotes active TB disease. Thus, routine intestinal helminth screening and assessment of their nutritional status is suggested for TB patients.
CRIS-Team Scopus Importer:2023-11-10
Keywords: Africa; Asia; Co-infection; Intestinal helminths; Pooled prevalence; Tuberculosis

Intestinal Helminth Infections and Their Association with QuantiFERON-TB Gold Plus Test Performance in an Endemic Setting, Northwest Ethiopia - Zenebe, Yohannes; Abebe, Markos; Munshea, Abaineh; Yismaw, Gizachew; Zewde, Meaza; Alemayehu, Mekdelawit; Lang, Roland; Habtamu, Meseret (Infection and Drug Resistance, 2024)
Background: Timely detection and treatment of latent TB infection (LTBI) is part of WHO’s strategy against tuberculosis (TB). Helminth infections can modulate immune responses, potentially impacting the performance of interferon-gamma release assays (IGRAs) such as the QuantiFERON-TB Gold Plus (QFT-Plus). This study evaluated the association between helminth infections and QFT-Plus results among participants from a TB-endemic region. Methods: A cross-sectional study was conducted from October 2022 to March 2023 in Bahir Dar, Ethiopia. Stool samples of 314 potential participants were examined for helminths using wet mount and Kato-Katz techniques. LTBI was assessed by QFT-Plus from a total of 100 gender-matched helminth-positive and-negative participants. The association between helminth infection status, egg count, and QFT-Plus positivity was analyzed, and p values <0.05 were considered significant. Results: Overall, 53 of 314 screened participants were infected with helminths (16.9%), with A. lumbricoides (47.2%) and hookworm (30.2%) as most prevalent species. The overall QFT-Plus positivity rate was 30.0%, with similar rates observed between helminth-positive and helminth-negative participants. Although QFT-Plus positivity was slightly lower in hookworm carriers (25%) compared to those with A. lumbricoides (32%), a higher-than-median hookworm egg burden was significantly associated with reduced QFT-Plus positivity (P = 0.029). QFT-Plus positivity was significantly higher among male participants than females (P = 0.032). Conclusion: While overall helminth infection status did not significantly affect QFT-Plus positivity, higher hookworm burden was associated with reduced QFT-Plus reactivity. These findings suggest that the type of helminth and infection intensity, rather than its mere presence, may influence IGRA performance. Further studies with larger sample sizes are warranted to understand the species-specific effect of helminth infection on immune modulation of the host.
CRIS-Team Scopus Importer:2024-11-08
Keywords: Ethiopia; intestinal helminths; LTBI; MTB; QFT-Plus

Intestinal tumorigenesis initiated by dedifferentiation and acquisition of stem-cell-like properties - Schwitalla, Sarah; Fingerle, Alexander A.; Cammareri, Patrizia; Nebelsiek, Tim; Goektuna, Serkan I.; Ziegler, Paul K.; Canli, Ozge; Heijmans, Jarom; Huels, David J.; Moreaux, Guenievre; Rupec, Rudolf A.; Gerhard, Markus; et al. (Cell, 2013)
Cell-type plasticity within a tumor has recently been suggested to cause a bidirectional conversion between tumor-initiating stem cells and nonstem cells triggered by an inflammatory stroma. NF-κB represents a key transcription factor within the inflammatory tumor microenvironment. However, NF-κB's function in tumor-initiating cells has not been examined yet. Using a genetic model of intestinal epithelial cell (IEC)-restricted constitutive Wnt-activation, which comprises the most common event in the initiation of colon cancer, we demonstrate that NF-κB modulates Wnt signaling and show that IEC-specific ablation of RelA/p65 retards crypt stem cell expansion. In contrast, elevated NF-κB signaling enhances Wnt activation and induces dedifferentiation of nonstem cells that acquire tumor-initiating capacity. Thus, our data support the concept of bidirectional conversion and highlight the importance of inflammatory signaling for dedifferentiation and generation of tumor-initiating cells in vivo.
EVALuna2:7625

Limitation of TCA Cycle Intermediates Represents an Oxygen-Independent Nutritional Antibacterial Effector Mechanism of Macrophages - Hayek, Inaya; Fischer, Fabian; Schulze-Luehrmann, Jan; Dettmer, Katja; Sobotta, Katharina; Schatz, Valentin; Kohl, Lisa; Boden, Katharina; Lang, Roland; Oefner, Peter J.; Wirtz, Stefan; Jantsch, Jonathan; et al. (Cell Reports, 2019)
In hypoxic and inflamed tissues, oxygen (O-2)-dependent antimicrobial defenses are impaired due to a shortage of O-2. To gain insight into the mechanisms that control bacterial infection under hypoxic conditions, we infected macrophages with the obligate intracellular pathogen Coxiella burnetii, the causative agent of Q fever. Our experiments revealed that hypoxia impeded C. burnetii replication in a hypoxia-inducible factor (HIF) 1 alpha-dependent manner. Mechanistically, under hypoxia, HIF1 alpha impaired the activity of STAT3, which in turn reduced the intracellular level of TCA cycle intermediates, including citrate, and impeded C. burnetii replication in macrophages. However, bacterial viability was maintained, allowing the persistence of C. burnetii, which is a prerequisite for the development of chronic Q fever. This knowledge will open future research avenues on the pathogenesis of chronic Q fever. In addition, the regulation of TCA cycle metabolites by HIF1 alpha represents a previously unappreciated mechanism of host defense against intracellular pathogens.
CRIS-Team WoS Importer:2019-04-09

Macrophage phosphoproteome analysis reveals MINCLE-dependent and -independent mycobacterial cord factor signaling - Hansen, M.; Peltier, J.; Killy, B.; Trost, M.; Lang, Roland (EUROPEAN JOURNAL OF IMMUNOLOGY, 2019)
CRIS-Team WoS Importer:2019-10-08

Macrophage phosphoproteome analysis reveals MINCLE-dependent and-independent mycobacterial cord factor signaling - Hansen, Madlen; Peltier, Julian; Killy, Barbara; Amin, Bushra; Bodendorfer, Barbara; HäRtlova, Anetta; Uebel, Sebastian; Bosmann, Markus; Hofmann, Jörg; Büttner, Christian; Ekici, Arif Bülent; Kuttke, Mario; et al. (Molecular & Cellular Proteomics, 2019)
Immune sensing of Mycobacterium tuberculosis relies on recognition by macrophages. Mycobacterial cord factor, trehalose-6,6-dimycolate (TDM), is the most abundant cell wall glycolipid and binds to the C-type lectin receptor (CLR) MINCLE. To explore the kinase signaling linking the TDM-MINCLE interaction to gene expression, we employed quantitative phosphoproteome analysis. TDM caused upregulation of 6.7% and suppressed 3.8% of the 14,000 phospho-sites identified on 3727 proteins. MINCLE-dependent phosphorylation was observed for canonical players of CLR signaling (e.g. PLC, PKC), and was enriched for PKC and GSK3 kinase motifs. MINCLE-dependent activation of the PI3K-AKT-GSK3 pathway contributed to inflammatory gene expression and required the PI3K regulatory subunit p85. Unexpectedly, a substantial fraction of TDM-induced phosphorylation was MINCLE-independent, a finding paralleled by transcriptome data. Bioinformatics analysis of both data sets concurred in the requirement for MINCLE for innate immune response pathways and processes. In contrast, MINCLE-independent phosphorylation and transcriptome responses were linked to cell cycle regulation. Collectively, our global analyses show substantial reprogramming of macrophages by TDM and reveal a dichotomy of MINCLE-dependent and-independent signaling linked to distinct biological responses.
CRIS-Team Scopus Importer:2019-05-02

Macrophages inhibit Coxiella burnetii by the ACOD1-itaconate pathway for containment of Q fever - Kohl, Lisa; Siddique, Md Nur A Alam; Bodendorfer, Barbara; Berger, Raffaela; Preikschat, Annica; Daniel, Christoph; Ölke, Martha; Liebler-Tenorio, Elisabeth; Schulze-Lührmann, Jan; Mauermeir, Michael; Yang, Kai-Ting; Hayek, Inaya; et al. (Embo Molecular Medicine, 2022)
Infection with the intracellular bacterium Coxiella (C.) burnetii can cause chronic Q fever with severe complications and limited treatment options. Here, we identify the enzyme cis-aconitate decarboxylase 1 (ACOD1 or IRG1) and its product itaconate as protective host immune pathway in Q fever. Infection of mice with C. burnetii induced expression of several anti-microbial candidate genes, including Acod1. In macrophages, Acod1 was essential for restricting C. burnetii replication, while other antimicrobial pathways were dispensable. Intratracheal or intraperitoneal infection of Acod1−/− mice caused increased C. burnetii burden, weight loss and stronger inflammatory gene expression. Exogenously added itaconate restored pathogen control in Acod1−/− mouse macrophages and blocked replication in human macrophages. In axenic cultures, itaconate directly inhibited growth of C. burnetii. Finally, treatment of infected Acod1−/− mice with itaconate efficiently reduced the tissue pathogen load. Thus, ACOD1-derived itaconate is a key factor in the macrophage-mediated defense against C. burnetii and may be exploited for novel therapeutic approaches in chronic Q fever.
CRIS-Team Scopus Importer:2022-12-16
Keywords: Cis-aconitate decarboxylase 1; Coxiella burnetii; Immune responsive gene 1; immunometabolism; itaconate

Measurement of TLR-induced macrophage spreading by automated image analysis: Differential role of Myd88 and MAPK in early and late responses - Wenzel, Jens; Held, Christian; Palmisano, Ralf; Teufel, S.; David, Jean Pierre; Wittenberg, Thomas; Lang, Roland (Frontiers in Physiology, 2011)
Sensing of infectious danger by toll-like receptors (TLRs) on macrophages causes not only a reprogramming of the transcriptome but also changes in the cytoskeleton important for cell spreading and motility. Since manual determination of cell contact areas from fluo-, rescence micrographs is very time-consuming and prone to bias, we have developed and tested algorithms for automated measurement of macrophage spreading. The two-step method combines identification of cells by nuclear staining with DAPI and cell surface staining of the integrin CD11b. Automated image analysis correlated very well with manual annotation in resting macrophages and early after stimulation, whereas at later time points the automated cell segmentation algorithm and manual annotation showed slightly larger variation. The method was applied to investigate the impact of genetic or pharmacological inhibition of known TLR signaling components. Deficiency in the adapter protein Myd88 strongly reduced spreading activity at the late time points, but had no impact early after LPS-stimulation. A similar effect was observed upon pharmacological inhibition of MEK1, the kinase activating the mitogen-activated protein kinases (MAPK) ERK1/2, indicating that ERK1/2 mediates Myd88-dependent macrophages spreading. In contrast, macrophages lacking the MAPK p38 were impaired in the initial spreading response but responded normally 8-24 h after stimulation. The dichotomy of p38 and ERK1/2 MAPK effects on early and late macrophage spreading raises the question which of the respective substrate proteins mediate(s) cytoskeletal remodeling and spreading. The automated measurement of cell spreading described here increases the objectivity and greatly reduces the time required for such investigations and is therefore expected to facilitate larger throughput analysis of macrophage spreading, e.g., in siRNA knockdown screens. © 2011 Wenzel, Held, Palmisano, Teufel, David, Wittenberg and Lang.

Meningitis and intracranial abscess due to Mycoplasma pneumoniae in a B cell-depleted patient with multiple sclerosis - Madžar, Dominik; Nickel, Florian; Rothhammer, Veit; Gölitz, Philipp; Geißdörfer, Walter; Dumke, Roger; Lang, Roland (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Mycoplasma pneumoniae, a frequent respiratory pathogen, can cause neurological disease manifestations. We here present a case of M. pneumoniae as cause of meningitis and occurrence of an intracranial abscess as a complication of mastoiditis with septic cerebral venous sinus thrombosis in a patient with multiple sclerosis on anti-CD20 therapy.
CRIS-Team Scopus Importer:2024-09-20
Keywords: Abscess; Anti-CD20 antibody; Complication; Mastoiditis; Multiple sclerosis; Mycoplasma pneumoniae; Ocrelizumab; Rituximab; Septic cerebral venous sinus thrombosis

Mincle-mediated anti-inflammatory IL-10 response counter-regulates IL-12 in vitro - Patin, Emmanuel C.; Willcocks, Sam; Orr, Selinda; Ward, Theresa H.; Lang, Roland; Schaible, Ulrich E. (Innate Immunity, 2016)
The role of macrophage-inducible C-type lectin (Mincle) in anti-inflammatory responses has not yet been fully characterized. Herein, we show that engagement of Mincle by trehalose-dimycolate or mycobacteria promotes IL-10 production in macrophages, which causes down-regulation of IL-12p40 secretion. Thus, Mincle mediates both pro- as well as anti-inflammatory responses.
EVALuna2:7704

Molecular diagnosis of polymicrobial brain abscesses with 16S-rDNA-based next-generation sequencing - Stebner, Alexander; Enßer, Armin; Geißdörfer, Walter; Bozhkov, Yavor; Lang, Roland (Clinical Microbiology and Infection, 2020)
Objectives: Brain abscesses lead to high mortality despite antibiotic and surgical treatment. Identification of causative bacteria is important to guide antibiotic therapy, but culture-based methods and molecular diagnostics by Sanger sequencing of 16S PCR products are hampered by antibiotic treatment and the often polymicrobial nature of brain abscesses. We have applied 16S-rRNA-based next-generation sequencing (NGS) for metagenomic analysis of intracranial abscess (brain and epidural) and meningitis samples. Methods: Seventy-nine samples from 54 patients with intracranial abscesses or meningitis were included. DNA was subjected to 16S PCR. Amplicons were analysed with the Illumina MiSeq system, sequence reads were blasted versus the NCBI 16S bacterial database and analysed using MEGAN software. Results were compared to those of gram-staining, culture and Sanger sequencing. Results: The NGS workflow was successful for 51 intracranial abscesses (46 brain and five epidural) and nine meningitis samples. Inclusion of (mono)bacterial meningitis samples allowed us to establish a cut-off criterion for the exclusion of contaminating sequences. In total 86 bacterial taxa were identified in brain abscesses by NGS, with Streptococcus intermedius and Fusobacterium nucleatum as most prevalent species; Propionibacterium and Staphylococcus spp. were associated with epidural abscesses. NGS identified two or more bacterial taxa in 31/51 intracranial abscesses, revealing the polymicrobial nature of these infections and allowing the discrimination of up to 16 bacterial taxa per sample. Conclusion: These results extend earlier studies showing that NGS methods expand the spectrum of bacteria detected in brain abscesses and demonstrate that the MiSeq platform is suitable for metagenomic diagnostics of this severe infection.
CRIS-Team Scopus Importer:2020-04-28
Keywords: 16S rDNA; Brain abscess; Metagenome; Next-generation sequencing; Polymicrobial infection

Monocytes Elicit a Neutrophil-Independent Th1/Th17 Response Upon Immunization With a Mincle-Dependent Glycolipid Adjuvant - Desel, Christiane; Murray, Peter J.; Lehmann, Christian; Heger, Lukas; Christensen, Dennis; Andersen, Peter; Mack, Matthias; Dudziak, Diana; Lang, Roland (Frontiers in Immunology, 2022)
Successful subunit vaccination with recombinant proteins requires adjuvants. The glycolipid trehalose-dibehenate (TDB), a synthetic analog of the mycobacterial cord factor, potently induces Th1 and Th17 immune responses and is a candidate adjuvant for human immunization. TDB binds to the C-type lectin receptor Mincle and triggers Syk-Card9-dependent APC activation. In addition, interleukin (IL)-1 receptor/MyD88-dependent signaling is required for TDB adjuvanticity. The role of different innate immune cell types in adjuvant-stimulated Th1/Th17 responses is not well characterized. We investigated cell recruitment to the site of injection (SOI) and to the draining lymph nodes (dLNs) after immunization with the TDB containing adjuvant CAF01 in a protein-based vaccine. Recruitment of monocytes and neutrophils to the SOI and the dramatic increase in lymph node cellularity was partially dependent on both Mincle and MyD88. Despite their large numbers at the SOI, neutrophils were dispensable for the induction of Th1/Th17 responses. In contrast, CCR2-dependent monocyte recruitment was essential for the induction of Th1/Th17 cells. Transport of adjuvant to the dLN did not require Mincle, MyD88, or CCR2. Together, adjuvanticity conferred by monocytes can be separated at the cellular level from potential tissue damage by neutrophils.
CRIS-Team WoS Importer:2022-06-03

Mycobacterial Cord Factor Reprograms the Macrophage Response to IFN-γ towards Enhanced Inflammation yet Impaired Antigen Presentation and Expression of GBP1 - Huber, Alexandra; Killy, Barbara; Grummel, Nadine; Bodendorfer, Barbara; Paul, Sushmita; Wiesmann, Veit; Naschberger, Elisabeth; Zimmer, Jana; Wirtz, Stefan; Schleicher, Ulrike; Vera, Julio; Ekici, Arif Bülent; et al. (Journal of Immunology, 2020)
Mycobacteria survive in macrophages despite triggering pattern recognition receptors and T cell-derived IFN-γ production. Mycobacterial cord factor trehalose-6,6-dimycolate (TDM) binds the C-type lectin receptor MINCLE and induces inflammatory gene expression. However, the impact of TDM on IFN-γ-induced macrophage activation is not known. In this study, we have investigated the cross-regulation of the mouse macrophage transcriptome by IFN-γ and by TDM or its synthetic analogue trehalose-6,6-dibehenate (TDB). As expected, IFN-γ induced genes involved in Ag presentation and antimicrobial defense. Transcriptional programs induced by TDM and TDB were highly similar but clearly distinct from the response to IFN-γ. The glycolipids enhanced expression of a subset of IFN-γ-induced genes associated with inflammation. In contrast, TDM/TDB exerted delayed inhibition of IFN-γ-induced genes, including pattern recognition receptors, MHC class II genes, and IFN-γ-induced GTPases, with antimicrobial function. TDM downregulated MHC class II cell surface expression and impaired T cell activation by peptide-pulsed macrophages. Inhibition of the IFN-γ-induced GTPase GBP1 occurred at the level of transcription by a partially MINCLE-dependent mechanism that may target IRF1 activity. Although activation of STAT1 was unaltered, deletion of Socs1 relieved inhibition of GBP1 expression by TDM. Nonnuclear Socs1 was sufficient for inhibition, suggesting a noncanonical, cytoplasmic mechanism. Taken together, unbiased analysis of transcriptional reprogramming revealed a significant degree of negative regulation of IFN-γ-induced Ag presentation and antimicrobial gene expression by the mycobacterial cord factor that may contribute to mycobacterial persistence.
CRIS-Team Scopus Importer:2020-09-18

MyD88 Is Required for Efficient Control of Coxiella burnetii Infection and Dissemination - Kohl, Lisa; Hayek, Inaya; Daniel, Christoph; Schulze-Luehrmann, Jan; Bodendorfer, Barbara; Lührmann, Anja; Lang, Roland (Frontiers in Immunology, 2019)
The intracellular pathogen Coxiella (C.) burnetii causes Q fever, a usually self-limiting respiratory infection that becomes chronic and severe in some patients. Innate immune recognition of C. burnetii and its role in the decision between resolution and chronicity is not understood well. However, TLR2 is important for the response to C. burnetii in mice, and genetic polymorphisms in Myd88 have been associated with chronic Q fever in humans. Here, we have employed MyD88-deficient mice in infection models with the attenuated C. burnetii Nine Mile phase II strain (NMII). Myd88(-/-) macrophages failed to restrict the growth of NMII in vitro, and to upregulate production of the cytokines TNF, IL-6, and IL-10. Following intraperitoneal infection, NMII bacterial burden was significantly higher on day 5 and 20 in organs of Myd88(-/-) mice. After infection via the natural route by intratracheal injection, a higher bacterial load in the lung and increased dissemination of NMII to other organs was observed in MyD88-deficient mice. While wild-type mice essentially cleared NMII on day 27 after intratracheal infection, it was still readily detectable on day 42 in multiple organs in the absence of MyD88. Despite the elevated bacterial load, Myd88(-/-) mice had less granulomatous inflammation and expressed significantly lower levels of chemoattractants, inflammatory cytokines, and of several IFN gamma-induced genes relevant for control of intracellular pathogens. Together, our results show that MyD88-dependent signaling is essential for early control of C. burnetii replication and to prevent systemic spreading. The continued presence of NMII in the organs of Myd88(-/-) mice constitutes a new mouse model to study determinants of chronicity and resolution in Q fever.
CRIS-Team WoS Importer:2019-02-21

Of mice and men: Interaction of Corynebacterium diphtheriae strains with murine and human phagocytes - Weerasekera, Dulanthi; Fastner, Tamara Antonia; Lang, Roland; Burkovski, Andreas; Ott, Lisa (Virulence, 2019)
Seven non-toxigenic C. diphtheriae strains and one toxigenic strain were analyzed with regard to their interaction with murine macrophages (BMM) and human THP-1 macrophage-like cells. Proliferation assays with BMM and THP-1 revealed similar intracellular CFUs for C. diphtheriae strains independent of the host cell. Strain ISS4060 showed highest intracellular CFUs, while the toxigenic DSM43989 was almost not detectable. This result was confirmed by TLR 9 reporter assays, showing a low signal for DSM43989, indicating that the bacteria are not endocytosed. In contrast, the non-pathogenic C. glutamicum showed almost no intracellular CFUs independent of the host cell, but was recognized by TLR9, indicating that the bacteria were degraded immediately after endocytosis. In terms of G-CSF and IL-6 production, no significant differences between BMM and THP-1 were observed. G-CSF production was considerably higher than IL-6 for all C. diphtheriae strains and the C. glutamicum did not induce high cytokine secretion in general. Furthermore, all corynebacteria investigated in this study were able to induce NFκB signaling but only viable C. diphtheriae strains were able to cause host cell damage, whereas C. glutamicum did not. The absence of Mincle resulted in reduced G-CSF production, while no influence on the uptake of the bacteria was observed. In contrast, when MyD88 was absent, both the uptake of the bacteria and cytokine production were blocked. Consequently, phagocytosis only occurs when the TLR/MyD88 pathway is functional, which was also supported by showing that all corynebacteria used in this study interact with human TLR2.
CRIS-Team Scopus Importer:2019-06-04
Keywords: Cytotoxicity; inflammation; interleukins; macrophages; NFκB; TLRs

Osteocyte necrosis triggers osteoclast-mediated bone loss through macrophage-inducible C-type lectin - Andreev, Darja; Liu, Mengdan; Weidner, Daniela; Kachler, Katerina; Faas, Maria; Grüneboom, Anika; Schlötzer-Schrehardt, Ursula; Munoz, Luis Enrique; Steffen, Ulrike; Grötsch, Bettina; Killy, Barbara; Krönke, Gerhard; et al. (Journal of Clinical Investigation, 2020)
Although the control of bone-resorbing osteoclasts through osteocyte-derived RANKL is well defined, little is known about the regulation of osteoclasts by osteocyte death. Indeed, several skeletal diseases, such as bone fracture, osteonecrosis, and inflammation are characterized by excessive osteocyte death. Herein we show that osteoclasts sense damageassociated molecular patterns (DAMPs) released by necrotic osteocytes via macrophage-inducible C-type lectin (Mincle), which induced their differentiation and triggered bone loss. Osteoclasts showed robust Mincle expression upon exposure to necrotic osteocytes in vitro and in vivo. RNA sequencing and metabolic analyses demonstrated that Mincle activation triggers osteoclastogenesis via ITAM-based calcium signaling pathways, skewing osteoclast metabolism toward oxidative phosphorylation. Deletion of Mincle in vivo effectively blocked the activation of osteoclasts after induction of osteocyte death, improved fracture repair, and attenuated inflammation-mediated bone loss. Furthermore, in patients with osteonecrosis, Mincle was highly expressed at skeletal sites of osteocyte death and correlated with strong osteoclastic activity. Taken together, these data point to what we believe is a novel DAMP-mediated process that allows osteoclast activation and bone loss in the context of osteocyte death.
CRIS-Team Scopus Importer:2020-10-16

Phosphatidylinositol 3-Kinase (PI3K) Orchestrates Aspergillus fumigatus-Induced Eosinophil Activation Independently of Canonical Toll-Like Receptor (TLR)/C-Type-Lectin Receptor (CLR) Signaling - Dietschmann, Axel; Schrüfer, Sebastian; Westermann, Stefanie; Henkel, Fiona; Castiglione, Kirstin; Willebrand, Ralf; Adam, Jasmin; Ruland, Jurgen; Lang, Roland; Sheppard, Donald C.; Esser-Von-Bieren, Julia; Radtke, Daniel; et al. (Mbio, 2022)
Eosinophilia is associated with various persisting inflammatory diseases and often coincides with chronic fungal infections or fungal allergy as in the case of allergic bronchopulmonary aspergillosis (ABPA). Here, we show that intranasal administration of live Aspergillus fumigatus conidia causes fatal lung damage in eosinophilic interleukin-5 (IL-5)-transgenic mice. To further investigate the activation of eosinophils by A. fumigatus, we established a coculture system of mouse bone marrow-derived eosinophils (BMDE) with different A. fumigatus morphotypes and analyzed the secretion of cytokines, chemokines, and eicosanoids. A. fumigatus-stimulated BMDE upregulated expression of CD11b and downregulated CD62L and CCR3. They further secreted several proinflammatory mediators, including IL-4, IL-13, IL-18, macrophage inflammatory protein-1 alpha (MIP-1 alpha)/CC chemokine ligand 3 (CCL3), MIP-1 beta/CCL4, and thromboxane. This effect required direct interaction and adherence between eosinophils and A. fumigatus, as A. fumigatus culture supernatants or A. fumigatus mutant strains with impaired adhesion elicited a rather poor eosinophil response. Unexpectedly, canonical Toll-like receptor (TLR) or C-type-lectin receptor (CLR) signaling was largely dispensable, as the absence of MYD88, TRIF, or caspase recruitment domain-containing protein 9 (CARD9) resulted in only minor alterations. However, transcriptome analysis indicated a role for the PI3K-AKT-mTOR pathway in A. fumigatus-induced eosinophil activation. Correspondingly, we could show that phosphatidylinositol 3-kinase (PI3K) inhibitors successfully prevent A. fumigatus-induced eosinophil activation. The PI3K pathway in eosinophils may therefore serve as a potential drug target to interfere with undesired eosinophil activation in fungus-elicited eosinophilic disorders. IMPORTANCE Allergic bronchopulmonary aspergillosis (ABPA) is caused by the fungus Aspergillus fumigatus, afflicts about five million patients globally, and is still a noncurable disease. ABPA is associated with pronounced lung eosinophilia. Activated eosinophils enhance the inflammatory response not only by degranulation of toxic proteins but also by secretion of small effector molecules. Receptors and signaling pathways involved in activation of eosinophils by A. fumigatus are currently unknown. Here, we show that A. fumigatus-elicited activation of eosinophils requires direct cell-cell contact and results in modulation of cell surface markers and rapid secretion of cytokines, chemokines, and lipid mediators. Unexpectedly, this activation occurred independently of canonical Toll-like receptor or C-type lectin receptor signaling. However, transcriptome analysis indicated a role for the PI3K-AKT-mTOR pathway, and PI3K inhibitors successfully prevented A. fumigatus-induced eosinophil activation. The PI3K pathway may therefore serve as a potential drug target to interfere with undesired eosinophil activation in fungus-elicited eosinophilic disorders.
CRIS-Team WoS Importer:2022-06-24

PI3K signaling orchestrates eosinophil activation against Aspergillus fumigatus independently of canonical TLR/CLR signaling - Dietschmann, Axel; Schrüfer, Sebastian; Westermann, Stefanie; Henkel, F.; Castiglione, Kathrin; Willebrand, Ralf; Ruland, J.; Lang, Roland; Esser-Von-Bieren, J.; Radtke, Daniel; Krappmann, Sven; Vöhringer, David (MYCOSES, 2021)
CRIS-Team WoS Importer:2021-10-08

Pleural Resident Macrophages and Pleural IRA B Cells Promote Efficient Immunity Against Pneumonia by Inducing Early Pleural Space Inflammation - Benard, Alan; Podolska, Malgorzata; Czubayko, Franziska; Kutschick, Isabella; Klösch, Bettina; Jacobsen, Anne; Naschberger, Elisabeth; Brunner, Maximilian; Krautz, Christian; Trufa, Denis; Sirbu, Horia; Lang, Roland; et al. (Frontiers in Immunology, 2022)
Airway infection is a major cause of mortality worldwide. The identification of new mechanisms aiding in effective host immune response is therefore required. Here, we show that the specific depletion of the pleural immune cell compartment during bacterial pneumonia resulted in a reduced pulmonary immune response and increased mortality in mice. Bacterial airway infection provoked early pleural space (PS) inflammation characterized by innate response activator (IRA) B cell development and pleural large resident macrophage (LRM) necroptosis, the repopulation of LRMs being driven by cellular proliferation in situ. Necroptotic LRMs amplified PS inflammation by stimulating pleural Mincle-expressing macrophages whereas IRA B cells contributed partially to GM-CSF-induced PS inflammation. Upon pulmonary infection, the induction of PS inflammation resulted in reduced bacterial burden whereas the specific depletion of pleural resident macrophages led to increased mortality and bacterial burden and reduced pulmonary immunity. Moreover, mice in which B cells were unable to produce GM-CSF exhibited reduced CD103+ dendritic cells and reduced CD4+ T cell numbers in the draining lymph node. Altogether, our results describe a previously unrecognized mechanism of pleural space inflammation necessary for effective protection against bacterial airway infection.
CRIS-Team Scopus Importer:2022-05-13
Keywords: bacterial airway infection; IRA B cells; mincle; necroptosis; pleural resident macrophages; pleural space

Proteomics of diphtheria toxoid vaccines reveals multiple proteins that are immunogenic and may contribute to protection of humans against Corynebacterium diphtheriae - Möller, Jens; Kraner, Max; Sonnewald, Uwe; Sangal, Vartul; Tittlbach, Hannes; Winkler, Julia; Winkler, Thomas; Melnikov, Vyacheslav; Lang, Roland; Sing, Andreas; Mattos-Guaraldi, Ana Luiza; Burkovski, Andreas (Vaccine, 2019)
Introduced for mass immunization in the 1920s, vaccines against diphtheria are among the oldest and safest vaccines known. The basic principle of their production is the inactivation of purified diphtheria toxin by formaldehyde cross-linking, which converts the potentially fatal toxin in a completely harmless protein aggregate, which is still immunogenic. Since in addition to diphtheria toxin also other proteins may be secreted by Corynebacterium diphtheriae during cultivation, we assumed that diphtheria toxoid might not be the only component present in the vaccine. To address this question, we established a protocol to reverse formaldehyde cross-linking and carried out mass spectrometric analyses. Different secreted, membrane-associated and cytoplasmic proteins of C. diphtheriae were detected in several vaccine preparations from across the world. Based on these results, bioinformatics and Western blot analyses were applied to characterize if these proteins are immunogenic and may therefore support protection against C. diphtheriae. In frame of this study, we could show that the C. diphtheriae toxoid vaccines induce antibodies against different C. diphtheriae proteins and against diphtheria toxin secreted by Corynebacterium ulcerans, an emerging pathogen which is outnumbering C. diphtheriae as cause of diphtheria-like illness in Western Europe.
CRIS-Team Scopus Importer:2019-05-09
Keywords: Corynebacteria; Corynebacterium ulcerans; Exoproteome; Mass spectrometry; Proteomics; Secretome; Vaccination

Resolution and chronicity of Q-fever in the mouse model: Myd88-deficiency and overexpression of IL-10 impairs clearance of Coxiella burnetii Nine Mile Phase II - Kohl, Lisa; Lührmann, Anja; Lang, Roland (2017)
EVALuna2:33413

Review: Impact of Helminth Infection on Antimycobacterial Immunity-A Focus on the Macrophage - Lang, Roland; Schick, Judith (Frontiers in Immunology, 2017)
Successful immune control ofMycobacterium tuberculosis(MTB) requires robust CD4+T cell responses, with IFNγs as the key cytokine promoting killing of intracellular mycobacteria by macrophages. By contrast, helminth infections typically direct the immune system toward a type 2 response, characterized by high levels of the cytokines IL-4 and IL-10, which can antagonize IFNγ production and its biological effects. In many countries with high burden of tuberculosis, helminth infections are endemic and have been associated with increased risk to develop tuberculosis or to inhibit vaccination-induced immunity. Mechanistically, regulation of the antimycobacterial immune response by helminths has been mostly been attributed to the T cell compartment. Here, we review the current status of the literature on the impact of helminths on vaccine-induced and natural immunity to MTB with a focus on the alterations enforced on the capacity of macrophages to function as sensors of mycobacteria and effector cells to control their replication.
EVALuna2:33299

Selective Expression of the MAPK Phosphatase Dusp9/MKP-4 in Mouse Plasmacytoid Dendritic Cells and Regulation of IFN-? Production - Niedzielska, Magdalena; Mohamed Raffi, Faizal Ali; Tel, Jurjen; Muench, Sandra; Jozefowski, Katrin; Alati, Nour; Lahl, Katharina; Mages, Joerg; Billmeier, Ulrike; Schiemann, Matthias; Appelt, Uwe K.; Wirtz, Stefan; et al. (Journal of Immunology, 2015)
Plasmacytoid dendritic cells (pDCs) efficiently produce large amounts of type I IFN in response to TLR7 and TLR9 ligands, whereas conventional DCs (cDCs) predominantly secrete high levels of the cytokines IL-10 and IL-12. The molecular basis underlying this distinct phenotype is not well understood. In this study, we identified the MAPK phosphatase Dusp9/MKP-4 by transcriptome analysis as selectively expressed in pDCs, but not cDCs. We confirmed the constitutive expression of Dusp9 at the protein level in pDCs generated in vitro by culture with Flt3 ligand and ex vivo in sorted splenic pDCs. Dusp9 expression was low in B220(-) bone marrow precursors and was upregulated during pDC differentiation, concomitant with established pDC markers. Higher expression of Dusp9 in pDCs correlated with impaired phosphorylation of the MAPK ERK1/2 upon TLR9 stimulation. Notably, Dusp9 was not expressed at detectable levels in human pDCs, although these displayed similarly impaired activation of ERK1/2 MAPK compared with cDCs. Enforced retroviral expression of Dusp9 in mouse GM-CSF-induced cDCs increased the expression of TLR9-induced IL-12p40 and IFN-?, but not of IL-10. Conditional deletion of Dusp9 in pDCs was effectively achieved in Dusp9(flox/flox); CD11c-Cre mice at the mRNA and protein levels. However, the lack of Dusp9 in pDC did not restore ERK1/2 activation after TLR9 stimulation and only weakly affected IFN-? and IL-12p40 production. Taken together, our results suggest that expression of Dusp9 is sufficient to impair ERK1/2 activation and enhance IFN-? expression. However, despite selective expression in pDCs, Dusp9 is not essential for high-level IFN-? production by these cells.
EVALuna2:2008

Suppressor of Cytokine Signaling 3 in Macrophages Prevents Exacerbated Interleukin-6-Dependent Arginase-1 Activity and Early Permissiveness to Experimental Tuberculosis - Schmok, Erik; Dar, Mahin Abad; Behrends, Jochen; Erdmann, Hanna; Rueckerl, Dominik; Endermann, Tanja; Heitmann, Lisa; Hessmann, Manuela; Yoshimura, Akihiko; Rose-John, Stefan; Scheller, Juergen; Schaible, Ulrich Emil; et al. (Frontiers in Immunology, 2017)
Suppressor of cytokine signaling 3 (SOCS3) is a feedback inhibitor of interleukin (IL)-6 signaling in macrophages. In the absence of this molecule, macrophages become extremely prone to an IL-6-dependent expression of arginase-1 (Arg1) and nitric oxide synthase (NOS)2, the prototype markers for alternative or classical macrophage activation, respectively. Because both enzymes are antipodean macrophage effector molecules inMycobacterium tuberculosis(Mtb) infection, we assessed the relevance of SOCS3 for macrophage activation during experimental tuberculosis using macrophage-specific SOCS3-deficient (LysMcreSOCS3loxP/loxP) mice. Aerosol infection of LysMcreSOCS3loxP/loxPmice resulted in remarkably higher bacterial loads in infected lungs and exacerbated pulmonary inflammation. This increased susceptibility toMtbinfection was accompanied by enhanced levels of both classical and alternative macrophage activation. However, high Arg1 expression preceded the increased induction of NOS2 and at early time points of infection mycobacteria were mostly found in cells positive for Arg1. This sequential activation of Arg1 and NOS2 expression in LysMcreSOCS3loxP/loxPmice appears to favor the initial replication ofMtbparticularly in Arg1-positive cells. Neutralization of IL-6 inMtb-infected LysMcreSOCS3loxP/loxPmice reduced arginase activity and restored control of mycobacterial replication in LysMcreSOCS3loxP/loxPmice. Our data reveal an unexpected role of SOCS3 during experimental TB: macrophage SOCS3 restrains early expression of Arg1 and helps limitMtbreplication in resident lung macrophages, thereby limiting the growth of mycobacteria. Together, SOCS3 keeps IL-6-dependent divergent macrophage responses such asNos2andArg1expression under control and safeguard protective macrophage effector mechanisms.
EVALuna2:33300

The C-type lectin receptor Mincle binds to Streptococcus pneumoniae but plays a limited role in the anti-pneumococcal innate immune response - Rabes, Anne; Zimmermann, Stephanie; Reppe, Katrin; Lang, Roland; Seeberger, Peter H.; Suttorp, Norbert; Witzenrath, Martin; Lepenies, Bernd; Opitz, Bastian (PLoS ONE, 2015)
The innate immune system employs C-type lectin receptors (CLRs) to recognize carbohydrate structures on pathogens and self-antigens. The Macrophage-inducible C-type lectin (Mincle) is a FcR?-coupled CLR that was shown to bind to mycobacterial cord factor as well as certain fungal species. However, since CLR functions during bacterial infections have not yet been investigated thoroughly, we aimed to examine their function in Streptococcus pneumonia infection. Binding studies using a library of recombinantly expressed CLR-Fc fusion proteins indicated a specific, Ca2+-dependent, and serotype-specific binding of Mincle to S. pneumonia. Subsequent experiments with different Mincle-expressing cells as well as Mincle-deficient mice, however, revealed a limited role of this receptor in bacterial phagocytosis, neutrophil-mediated killing, cytokine production, and antibacterial immune response during pneumonia. Collectively, our results indicate that Mincle is able to recognize S. pneumonia but is not required for the anti-pneumococcal innate immune response.
EVALuna2:7656

The early bird catches the IL-2 in C-type lectin receptor-dependent activation of dendritic cells - Blamberg, Robert; Lang, Roland (Science Signaling, 2023)
The transcriptional response of macrophages and dendritic cells to stimulation of pattern recognition receptors can be unexpectedly distinct. In this issue of Science Signaling, Watanabe et al. demonstrate that IL-2 is differentially induced by the closely related C-type lectin receptors Dectin-2 and Mincle and reveal early signaling through the adaptor protein FcRγ as a critical mechanism.
CRIS-Team Scopus Importer:2023-03-24

The role of lipids in host microbe interactions - Lang, Roland; Mattner, Jochen (Frontiers in Bioscience, 2017)
Lipids are one of the major subcellular constituents and serve as signal molecules, energy sources, metabolic precursors and structural membrane components in various organisms. The function of lipids can be modified by multiple biochemical processes such as (de-)phosphorylation or (de-)glycosylation, and the organization of fatty acids into distinct cellular pools and subcellular compartments plays a pivotal role for the morphology and function of various cell populations. Thus, lipids regulate, for example, phagosome formation and maturation within host cells and thus, are critical for the elimination of microbial pathogens. Vice versa, microbial pathogens can manipulate the lipid composition of phagosomal membranes in host cells, and thus avoid their delivery to phagolysosomes. Lipids of microbial origin belong also to the strongest and most versatile inducers of mammalian immune responses upon engagement of distinct receptors on myeloid and lymphoid cells. Furthermore, microbial lipid toxins can induce membrane injuries and cell death. Thus, we will review here selected examples for mutual host-microbe interactions within the broad and divergent universe of lipids in microbial defense, tissue injury and immune evasion.
EVALuna2:7757

TNF is required for upregulation of Mincle expression and adjuvant activity in response to mycobacterial glycolipids. - Schick, J.; Lang, Roland; Schäfer, Johanna; Schleicher, Ulrike (EUROPEAN JOURNAL OF IMMUNOLOGY, 2019)
CRIS-Team WoS Importer:2019-10-08

TNF promotes DECTIN2 family C-type lectin receptor expression in human macrophages. - Haberkamp, Carl; Allabauer, Ida; Blaha, Niklas; Bodendorfer, Barbara; Cunningham, Sarah; Hörning, André; Lang, Roland (Journal of Leukocyte Biology, 2023)
TNF blockade constitutes an effective therapy for inflammatory bowel disease, yet increases the risk for infection, including active tuberculosis. The DECTIN2 family C-type lectin receptors MINCLE, MCL, and DECTIN2 sense mycobacterial ligands and activate myeloid cells. In mice, upregulation of DECTIN2 family C-type lectin receptor after stimulation with Mycobacterium bovis Bacille Calmette-Guérin requires TNF. Here, we investigated whether TNF controls inducible C-type lectin receptor expression in human myeloid cells. Monocyte-derived macrophages were stimulated with Bacille Calmette-Guérin and the TLR4 ligand lipopolysaccharide, and expression of C-type lectin receptor was analyzed. Bacille Calmette-Guérin and lipopolysaccharide strongly upregulated messenger RNA expression of DECTIN2 family C-type lectin receptor but not of DECTIN1. Bacille Calmette-Guérin and lipopolysaccharide also induced robust production of TNF. Recombinant TNF was sufficient to upregulate expression of DECTIN2 family C-type lectin receptor. Blocking TNF with the TNFR2-Fc fusion protein etanercept abrogated, as expected, the effect of recombinant TNF and impaired induction of DECTIN2 family C-type lectin receptor by Bacille Calmette-Guérin and lipopolysaccharide. Flow cytometry confirmed upregulation of MCL at the protein level by recombinant TNF and showed inhibition of Bacille Calmette-Guérin-induced MCL by etanercept. To investigate the impact of TNF on C-type lectin receptor expression in vivo, we analyzed peripheral blood mononuclear cells of patients with inflammatory bowel disease and observed downregulation of MINCLE and MCL expression after therapeutic TNF blockade. Together, TNF is sufficient to upregulate DECTIN2 family C-type lectin receptor in human myeloid cells and contributes to this process after encounter with Bacille Calmette-Guérin or lipopolysaccharide. Impaired C-type lectin receptor expression in patients receiving TNF blockade may dampen the sensing of microbes and defense against infection.
EVALuna2:531674
Keywords: MINCLE; MCL; DECTIN2; TNF blockade; mycobacteria; inflammatory bowel disease

Toll-like receptor 2 and mincle cooperatively sense corynebacterial cell wall glycolipids - Schick, Judith; Etschel, Philipp; Bailo, Rebeca; Ott, Lisa; Bhatt, Apoorva; Lepenies, Bernd; Kirschning, Carsten; Burkovski, Andreas; Lang, Roland (Infection and Immunity, 2017)
EVALuna2:7744

Trehalose diester glycolipids are superior to the monoesters in binding to Mincle, activation of macrophages in vitro and adjuvant activity in vivo - Huber, Alexandra; Kallerup, Rie S.; Korsholm, Karen S.; Franzyk, Henrik; Lepenies, Bernd; Christensen, Dennis; Foged, Camilla; Lang, Roland (Innate Immunity, 2016)
The T-cell adjuvanticity of mycobacterial cord factor trehalose 6,6'-dimycolate (TDM) is well established. The identification of the C-type lectin Mincle on innate immune cells as the receptor for TDM and its synthetic analogue trehalose 6,6'-dibehenate (TDB) has raised interest in development of synthetic Mincle ligands as novel adjuvants. Trehalose mono- (TMXs) and diesters (TDXs) with symmetrically shortened acyl chains [denoted by X: arachidate (A), stearate (S), palmitate (P), and myristate (M)] were tested. Upon stimulation of murine macrophages, G-CSF secretion and NO production were strongly augmented by all TDXs tested, in a wide concentration range. In contrast, the TMXs triggered macrophage activation only at high concentrations. Macrophage activation by all TDXs required Mincle, but was independent of MyD88. The superior capacity of TDXs for activating macrophages was paralleled by direct binding of TDXs, but not of TMXs, to a Mincle-Fc fusion protein. Insertion of a short polyethylene glycol between the sugar and acyl chain in TDS reduced Mincle-binding and macrophage activation. Immunization of mice with cationic liposomes containing the analogues demonstrated the superior adjuvant activity of trehalose diesters. Overall, immune activation in vitro and in vivo by trehalose esters of simple fatty acids requires two acyl chains of length and involves Mincle.
EVALuna2:7717

Trehalose dimycolate interferes with FcγR-mediated phagosome maturation through Mincle, SHP-1 and FcγRIIB signalling. - Patin, Emmanuel C.; Geffken, Anna C.; Willcocks, Sam; Leschczyk, Christoph; Haas, Albert; Nimmerjahn, Falk; Lang, Roland; Ward, Theresa H.; Schaible, Ulrich E. (PLoS ONE, 2017)
The causative agent of tuberculosis, Mycobacterium tuberculosis (M. tuberculosis), contains an abundant cell wall glycolipid and a crucial virulence factor, trehalose-6,6'-dimycolate (TDM). TDM causes delay of phagosome maturation and thus promotes survival of mycobacteria inside host macrophages by a not fully understood mechanism. TDM signals through the Monocyte-INducible C-type LEctin (Mincle), a recently identified pattern recognition receptor. Here we show that recruitment of Mincle by TDM coupled to immunoglobulin (Ig)G-opsonised beads during Fcγ receptor (FcγR)-mediated phagocytosis interferes with phagosome maturation. In addition, modulation of phagosome maturation by TDM requires SH2-domain-containing inositol polyphosphate 5' phosphatase (SHP-1) and the FcγRIIB, which strongly suggests inhibitory downstream signalling of Mincle during phagosome formation. Overall, our study reveals important mechanisms contributing to the virulence of TDM.

Tuning of adaptive immune responses by TNF at the level of C-type lectin receptor expression - Blamberg, Robert; Lang, Roland (EUROPEAN JOURNAL OF IMMUNOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-27

Two Cases of Severe Tick-Borne Encephalitis in Rituximab-Treated Patients in Germany: Implications for Diagnosis and Prevention - Steininger, Philipp; Bobinger, Tobias; Dietrich, Wenke; Lee, De-Hyung; Knott, Michael; Bogdan, Christian; Korn, Klaus; Lang, Roland (Open Forum Infectious Diseases, 2017)
Rituximab (RTX) has become a standard therapy for certain B cell malignancies and autoimmune diseases. We report 2 RTX-treated patients who developed severe tick-borne encephalitis virus (TBEV) infection. The inability to generate new antibody responses renders RTX-treated patients susceptible to TBEV, impedes laboratory diagnosis, and necessitates preventive vaccination in endemic areas.
EVALuna2:22593

USP18 lack in microglia causes destructive interferonopathy of the mouse brain - Goldmann, Tobias; Zeller, Nicolas; Raasch, Jenni; Kierdorf, Katrin; Frenzel, Kathrin; Ketscher, Lars; Basters, Anja; Staszewski, Ori; Brendecke, Stefanie M.; Spiess, Alena; Tay, Tuan Leng; Kreutz, Clemens; et al. (EMBO Journal, 2015)
Microglia are tissue macrophages of the central nervous system (CNS) that control tissue homeostasis. Microglia dysregulation is thought to be causal for a group of neuropsychiatric, neurodegenerative and neuroinflammatory diseases, called "microgliopathies". However, how the intracellular stimulation machinery in microglia is controlled is poorly understood. Here, we identified the ubiquitin-specific protease (Usp) 18 in white matter microglia that essentially contributes to microglial quiescence. We further found that microglial Usp18 negatively regulates the activation of Stat1 and concomitant induction of interferon-induced genes, thereby terminating IFN signaling. The Usp18-mediated control was independent from its catalytic activity but instead required the interaction with Ifnar2. Additionally, the absence of Ifnar1 restored microglial activation, indicating a tonic IFN signal which needs to be negatively controlled by Usp18 under non-diseased conditions. These results identify Usp18 as a critical negative regulator of microglia activation and demonstrate a protective role of Usp18 for microglia function by regulating the Ifnar pathway. The findings establish Usp18 as a new molecule preventing destructive microgliopathy.
EVALuna2:7686